Identification of potential mine sites for low-enthalpy geothermal energy extraction in Australia: a geospatial framework - C.S. Waravita; W.G.P. Kumari; J.S. Vinod; C. Jayasekara; Y. Han; R.K.S. Maleesha; L.T. White; P.G. Ranjith (Geothermics, 2026)

Green extractive desalination with natural deep eutectic solvents - Ping Keung Wong; Lok Wan Ng; Wei Han; Matthew Y. Lui (Desalination, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Soil moisture information in Southeast Australia – A review of long-term field measurements toward enhanced monitoring and predictive applications - I.P. Senanayake; I.-Y. Yeo; M. Khaki; G.R. Hancock; P.G. Dahlhaus; N.J. Robinson; S.-C. Han; J.P. Walker (Geoderma Regional, 2026)

Machine learning-based parameter adaptation approach for modeling hysteretic axial-shear-flexure interaction in RC columns - Zi-Nan Wu; Xiao-Lei Han; Ahmed Y. Elghazouli (Bulletin of Earthquake Engineering, 2026)
Reinforced concrete (RC) members subjected to seismic loading experience variable axial forces and shear spans, which induce axial–shear–flexural interaction that governs their hysteretic behavior. Existing interaction models rely on complex constitutive assumptions such as smeared crack formulations, resulting in high computational demand and convergence difficulties, limiting their applicability for system-level assessments. To address these limitations, this study proposes a machine learning (ML)-based parameter adaptation approach that embeds ML surrogate models into lumped plasticity formulations with an adaptive updating mechanism. The suggested framework enables skeleton and hysteretic parameters to be dynamically updated during the analysis in response to variations in axial load, shear span, and cumulative damage, thereby capturing both cyclic degradation and axial–shear–flexure interaction. The approach is implemented for RC columns through the development of an adaptive hysteretic model. Ensemble neural networks, optimized via a complexity-aware grid search, are trained on a database of 286 cyclic tests with a balanced distribution of flexure-, flexure–shear-, and shear-critical specimens. These surrogate models are integrated into OpenSees through cross-platform coupling of Python-based ML routines and C++ numerical analysis to develop the adaptive model. Examination of adaptive features, coupled with experimental validations, confirm the accuracy of the proposed approach in capturing hysteretic axial–shear–flexural interaction under varying axial loads and shear spans, while achieving superior predictive performance and markedly reduced computational demand compared with existing interaction models. The results show that neglecting axial–shear–flexural interaction may significantly overestimate deformation and energy dissipation capacities. To this end, the proposed approach is shown to provide a reliable and efficient method for incorporating these effects into seismic resilience assessments.

Autologous Cord Blood Mononuclear Cells Modulate Immunity and the Microbiota in Very Preterm Twins: A Randomized Trial - Zhuxiao Ren; Chuan Nie; Fang Xu; Weiwei Gao; Shumei Yang; Jiangxue Han; Wei Wei; Sophie Y. Yang; Qi Zhang; Jie Yang (Stem Cell Reviews and Reports, 2026)

Persistent disparities in head and neck cancer survival in the United States - Ella P. Jackert; Swar Vimawala; Liyang Tang; Daniel Kwon; Niels Kokot; Tamara Chambers; Uttam Sinha; Yang Chai; Lihua Liu; Albert Y. Han (Cancer Causes & Control, 2026)
Purpose Head and neck cancer (HNC) is a heterogenous disease with substantial mortality. This study assesses the long-term epidemiologic landscape, demographic disparities, and survival outcomes of HNC. Methods Adult patients with primary HNC were identified in the Surveillance, Epidemiology, and End Results (SEER) database by International Classification of Diseases for Oncology (ICD-O) codes. The primary outcomes of this study were overall survival (OS) and cancer-specific survival (CSS). Secondary outcomes included primary tumor site distributions and rates of surgery by race and ethnicity. Multivariable Cox regression modeling was utilized to determine predictors of all-cause and HNC-specific mortality. Results In this cohort of 117,893 head and neck cancer patients, significant racial and ethnic disparities were observed in tumor site, treatment, and outcomes. Black patients were less likely to receive surgery even when accounting for tumor subsite and stage (OR 0.672, 95% CI 0.641–0.705). Five-year overall survival (OS) and cause-specific survival (CSS) were lower in all minority groups ( p < 0.001), with Black patients showing the lowest OS (31.3%) and CSS (58.8%). Multivariable analysis confirmed race/ethnicity, low income (HR 1.043, 95% CI 1.018–1.068), and unmarried status (HR 1.327, 95% CI 1.305–1.350) as independent predictors of increased all-cause and HNC-specific mortality. Conclusion In this most comprehensive and up-to-date analysis of HNC, we demonstrate profound racial and ethnic disparities in tumor sites, treatments, and survival. This study provides critical evidence to guide health policy, resource allocation, and clinical practice aimed at closing longstanding equity gaps in head and neck cancer care.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Self-powered photosynthetic microalgae hydrogel for bioelectric–oxygen–hydrogen–ATP and vesicular Nanomedicine–synergized osteoarthritis mitigation - Yu-Wen Tseng; Pei-Wei Weng; Hsien-Tsung Lu; Chia-Hung Liu; Yan-Ting Chen; Shen-Han Wu; Hieu Trung Nguyen; Andrew E.-Y. Chuang (Chemical Engineering Journal, 2026)

Geothermal resource identification in Australia using shallow groundwater temperature data - Y. Han; L. T. White; W. G. P. Kumari; T. Murray (Australian Journal of Earth Sciences, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Analysis of Helium Monte Carlo Data for the ISS-CREAM Instrument - A. Bagga; S. Aggarwal; Y. Amare; D. Angelaszek; D.P. Bowman; Y.C. Chen; G.H. Choi; M. Copley; L. Derome; Z.M. Dorris; L. Eraud; J.H. Han; et al. (Advances in Space Research, 2026)

Impacts of climate and land-use change on ecosystem services in the agro-pastoral ecotone of western Liaoning - Y. Li; D. Ye; X. Han; S. Xia; J. Jin; X. Jiang; L. Lv (International Journal of Environmental Science and Technology, 2026)

Earthworms Enhance Global Soil Carbon Storage Through Microbial–Mineral Stabilization - Yuanyuan Li; Jiahui Liao; Peter B. Reich; Yu Fang; Jiajie Cao; Juanping Ni; Tingting Ren; Guobing Wang; Xiaoming Zou; Honghua Ruan; Han Y. H. Chen (Global Change Biology, 2026)
Earthworms play a dual role in the global carbon cycle: they accelerate organic matter decomposition yet are often associated with greater soil organic carbon (SOC) storage. However, uncertainty regarding the mechanisms and magnitudes through which earthworms concurrently influence SOC mineralization and stabilization has limited the integration of soil fauna into carbon models. Here, we synthesize 696 paired observations from 122 studies worldwide to resolve this uncertainty. On average, earthworms increase SOC by 5.4% (95% CI: 2.2%–9.1%), with effects strengthening over time under sustained plant‐derived carbon inputs. Earthworms enhance mineral‐associated organic carbon (MAOC) by 21.2%, while particulate organic carbon (POC) remains unchanged. These patterns suggest that earthworm activity promotes a transition from short‐term carbon mineralization to long‐term stabilization, likely mediated by the coupling of microbial processing and physical protection. Specifically, epigeic earthworms boost microbial biomass carbon, whereas endogeic species enhance macroaggregate formation, facilitating the incorporation of microbial necromass into MAOC. The magnitude and direction of these effects depend on sustained carbon inputs and earthworm functional type. Collectively, these results reconcile decades of conflicting evidence and provide the first quantitative global synthesis showing that earthworms increased soil carbon over time under sustained plant carbon inputs. This microbial–mineral formation pathway has direct implications for climate‐smart land management, soil biodiversity conservation, and the representation of earthworm bioturbation in global carbon models.

Economic and societal indicators in sustainable roadway rating systems – a comparative analysis - Shih-Hsien Yang; Nam Hoai Tran; Andrew S. Chang; Calista Y. Tsai; Han-Ruen Yueh (Environment, Development and Sustainability, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Optimization strategies for cultural landscape recreational safety patterns to mitigate urban heat risks - Y. Mao; H. Han; X. Meng; Y. Wan (International Journal of Environmental Science and Technology, 2026)

High Shear Wet Granulation Process Common Deficiencies Observed in Recently Submitted New and Abbreviated Drug Applications - Lixia Cai; Haitao Li; Hang Guo; Steve Y. Rhieu; Zhouxi Wang; Feiyan Jin; Qiang Han (AAPS PharmSciTech, 2026)

Assessment and design of restrained reinforced concrete beams subjected to hysteresis elongation effects - Zi-Nan Wu; Ahmed Y. Elghazouli; Xiao-Lei Han; Cunbiao Huang (Engineering Structures, 2026)

PM2.5 exposure risks in urban outdoor jogging: multiple environmental determinants and mitigation strategies - L. Han; Y. J. Qi; L. Luo; W. Ding; K. Li; W. Li; L. Y. Tang (International Journal of Environmental Science and Technology, 2026)

The analysis of road stormwater runoff pollution in the typical coastal city of Lianyungang, East China - H. Leng; H. Luo; R. Han; W. Wu; B. Song; Y. Zhao; B.-J. He (International Journal of Environmental Science and Technology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Assessing humic acid as natural surfactant in sustainable electrokinetic remediation of low-permeability soil contaminated with petroleum hydrocarbons - J. Han; Y. J. Nam; H.-M. Ro; M. Kim (International Journal of Environmental Science and Technology, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Evaluation of accuracy on bottom-up NH3 emissions and sensitivity of PM2.5 to emission control in South Korea - K.M. Han; C.H. Jung; C.H. Song; J. Yu; Y. Pan; S.J. Cho; S.D. Shim; J.-H. Koo; J.H. Woo; J. Madalipay; K.Y. Kim; H.S. Kim (Atmospheric Environment, 2025)

Warming Amplifies Responses of Soil Organic Carbon to Multiple Global Change Drivers - Yuan Sun; Xinli Chen; Chen Chen; Xiaoming Zou; Cuiting Wang; César Terrer; Han Y. H. Chen; Manuel Delgado‐Baquerizo; Honghua Ruan (Global Change Biology, 2025)
Soil organic carbon (SOC) is the largest terrestrial C reservoir on Earth, which plays a critical role in climate regulation. While global warming is a defining feature of anthropogenic climate change, its interactive effects with other global change drivers on the content of SOC remain unclear. For this study we conducted a global meta‐analysis of 2349 observations from 363 studies, which revealed that warming alone reduced SOC by 7.2% while synergistically amplifying responses to other drivers. It enhanced the effects of elevated CO 2 by 240% and those of nitrogen addition by 350%, while exacerbating drought‐induced losses by 340%. Noticeably, while warming revealed synergistic interactions with other drivers, the interactions between elevated CO 2 , nitrogen addition, and drought were additive. The responses of SOC consistently strengthened with treatment intensity and duration across diverse ranges of ecosystems, climates, and soil textures. These findings establish warming as a catalytic force that reshapes SOC dynamics under ongoing global change, with profound implications for terrestrial C‐climate feedbacks.

LP-35 Development of an Optimized in vitro model for Range Finding in Acute Inhalation Toxicity: An Alternative to MucilAir™ - J.Y. Park; I.J. Bang; Y. Han; G.E. Kim; J.E. Lim; J.H. Yu; J. Yoo; H.R. Kim (Toxicology Letters, 2025)

P29-12 Four-Week Repeated Inhalation Toxicity Study of SiO2-ZnO Mixed Nanoparticles in Sprague-Dawley Rats - Y.-J. Heo; M.-J. Yang; H.-Y. Han; H.J. Jin; G.J. Oh; G.-H. Bae; M.-K. Song (Toxicology Letters, 2025)

P31-21 Detection Methods for Injection-Induced Pseudoallergic Reactions - C. Liu; Y. Yi; C. Li; Y. Zhao; Y. Zhang; J. Han; J. Tian; C. Pan; L. Wang; S. Liu; L. Ma; A. Liang (Toxicology Letters, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Quantitative comparison of seasonal and diurnal characteristics for urban heat using meteorological monitoring data - Y. Gao; J. Zhao; L. Han (International Journal of Environmental Science and Technology, 2025)

A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Fluorinated Amino-acid-doped microarray-based biochemical patches Deciphers in-situ spatiotemporal dynamics amidst intricate Bio-Interfaces - Ru Zhang; Ran Duan; Deqi Yang; Haofan Wu; Bingfang Wang; Zhiqiang Chang; Jing Chen; Jing Dai; Yingying Lv; Yi Liu; Menahem Y. Rotenberg; Dandan Liang; et al. (Chemical Engineering Journal, 2025)

Researching the plant community characteristic of expressway slopes in mountain areas of Southern Shaanxi, China - Y. Yang; H. Han (International Journal of Environmental Science and Technology, 2025)

Mapping of paddy field by Sentinel-1 SAR images and cadastre data in Yunlin, Taiwan - Jui-Han Yang; Kuo-Hsin Tseng; Shu-Ling Chen; Ya-Lun Tsai; Ray. Y. Chuang; Aive Liibusk; Chi-Farn Chen (International Journal of Remote Sensing, 2025)

Lianas exhibit lower leaf drought resistance than trees in both tropical dry and wet forests in Thailand - Lu Han; Pimnara Tinprabat; Phisamai Maenpuen; Wirong Chanthorn; Dokrak Marod; Pantana Tor-ngern; Sathid Thinkampheang; Anuttara Nathalang; Warren Y. Brockelman; Shubin Zhang; Yajun Chen (Flora, 2025)

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhanced scar mitigation via hyperbaric oxygen therapy and immune modulation using nanoparticle-orchestrated photosynthetic chlorella in polysaccharide hydrogels - Wei-Yung Huang; Wen-Yu Pan; Shen-Han Wu; Hieu Trung Nguyen; Andrew E.-Y. Chuang (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Adsorption of cadmium ion from water by using non-toxic iron oxide adsorbent; experimental and statistical modelling analysis - D. Gusain; S. Sahani; Y. C. Sharma; S. S. Han (International Journal of Environmental Science and Technology, 2025)

Characterizing immune responses of grey mullet (Mugil cephalus) to Nocardia seriolae ex vivo and in vivo - Ya-Ting Wang; Chien-Yueh Lee; Ching-Hung Chan; Liang-Chuan Lai; Mong-Hsun Tsai; Eric Y. Chuang; Li-Han Chen (Aquaculture International, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Trends and classification of aerosol observed from MODIS sensor over Northern Europe and the Arctic - Kyung M. Han; Chang H. Jung; Chul H. Song; Ja H. Koo; Young J. Yoon; Bang Y. Lee; Hyun S. Kim; S. Seo (Atmospheric Pollution Research, 2025)

The impact of shared mobility on metro ridership: The non-linear effects of bike-sharing and ride-hailing services - Fan Gao; Sylvia Y. He; Chunyang Han; Jian Liang (Travel Behaviour and Society, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Assessing the physicochemical properties of surface/groundwater of Sudhnoti district, Azad Jammu and Kashmir: Impacts on lindane degradation by photocatalysis - Taj Ur Rahman; Lubna Saba; Ashraf Ali; Wajiha Liaqat; Sanaullah Khan; Javed Ali Khan; Muhammad Aurang Zeb; Sajjad Hussain; Eman Y. Santali; Changseok Han (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

P08-05 The Role and mechanism of O-GlcNAcylation in abnormalities of oocyte maturation and early embryonic development caused by PFOS exposure - Z. Wu; Q. Yuan; H. Qian; S. Han; Q. Xu; Y. Xia; Y. Fan; C. Lu (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Changes in the ability of Listeria monocytogenes to resist thermal treatment and simulated gastric condition after exposure to sequential stresses in minced meat - Hui Yang; Yujie Meng; Xintong Han; Xinru Meng; Baowei Yang; Chunling Zhang; Xin Wang; Jiangtao Yu; Fahad Al-Asmari; Anas S Dablool; Manal Y Sameeh; Chao Shi (Food Research International, 2024)

Development of polysaccharide-coated layered double hydroxide nanocomposites for enhanced oral insulin delivery - Huiwen Pang; Youzhi Wu; Yang Chen; Chen Chen; Xuqiang Nie; Peng Li; Guojun Huang; Zhi Ping Xu; Felicity Y. Han (Drug Delivery and Translational Research, 2024)
Oral insulin (INS) is predicted to have the most therapeutic advantages in treating diabetes to repress hepatic glucose production through its potential to mimic the endogenous insulin pathway. Many oral insulin delivery systems have been investigated. Layered double hydroxide (LDH) as an inorganic material has been widely used in drug delivery thanks to its appealing features such as good biocompatibility, low toxicity, and excellent loading capability. However, when used in oral drug delivery, the effectiveness of LDH is limited due to the acidic degradation in the stomach. In this study, to overcome these challenges, chitosan (Chi) and alginate (Alg) dual-coated LDH nanocomposites with the loading of insulin (Alg-Chi-LDH@INS) were developed by the layered-by-layered method for oral insulin delivery with dynamic size of ~ 350.8 nm, negative charge of ~ − 13.0 mV, and dispersity index 0.228. The insulin release profile was evaluated by ultraviolet–visible spectroscopy. The drug release profiles evidenced that alginate and chitosan coating partially protect insulin release from a burst release in acidic conditions. The analysis using flow cytometry showed that chitosan coating significantly enhanced the uptake of LDH@INS by Caco-2 cells compared to unmodified LDH and free insulin. Further in the in vivo study in streptozocin-induced diabetic mice, a significant hypoglycemic effect was maintained following oral administration with great biocompatibility (~ 50% blood glucose level reduction at 4 h). This research has thus provided a potential nanocomposite system for oral delivery of insulin. Graphical Abstract

Survival of biomass and waste power generation: A global overview - Wenyi Han; Wendy Y. Chen (Science of The Total Environment, 2024)

Effects of polymer matrix and temperature on pyrolysis of tetrabromobisphenol A: Product profiles and transformation pathways - Kai-Hui Zhang; Lian-Jun Bao; Yu Wang; Han-Ming Yang; Yanpeng Gao; Caiming Tang; Chen-Chou Wu; Eddy Y. Zeng (Journal of Hazardous Materials, 2024)

Sustainable regulation of calcium magnesium phosphate and rapeseed cake on soil-tea system in Mount Lushan, China - C. Han; Y. Ding; Z. J. Tang; Y. Q. Lai; M. Liu (Environmental Geochemistry and Health, 2024)

Emergent constraints on historical and future global gross primary productivity - Xin Chen; Tiexi Chen; Yi Y. Liu; Bin He; Shuci Liu; Renjie Guo; Han Dolman (Global Change Biology, 2024)
Terrestrial gross primary productivity (GPP) is the largest carbon flux in the global carbon cycle and plays a crucial role in terrestrial carbon sequestration. However, historical and future global GPP estimates still vary markedly. In this study, we reduced uncertainties in global GPP estimates by employing an innovative emergent constraint method on remote sensing‐based GPP datasets (RS‐GPP), using ground‐based estimates of GPP from flux towers as the observational constraint. Using this approach, the global GPP in 2001–2014 was estimated to be 126.8 ± 6.4 PgC year −1 , compared to the original RS‐GPP ensemble mean of 120.9 ± 10.6 PgC year −1 , which reduced the uncertainty range by 39.6%. Independent space‐ and time‐based (different latitudinal zones, different vegetation types, and individual year) constraints further confirmed the robustness of the global GPP estimate. Building on these insights, we extended our constraints to project global GPP estimates in 2081–2100 under various Shared Socioeconomic Pathway (SSP) scenarios: SSP126 (140.6 ± 9.3 PgC year −1 ), SSP245 (153.5 ± 13.4 PgC year −1 ), SSP370 (170.7 ± 16.9 PgC year −1 ), and SSP585 (194.1 ± 23.2 PgC year −1 ). These findings have important implications for understanding and projecting climate change, helping to develop more effective climate policies and carbon reduction strategies.

Enhancing green sea turtle (Chelonia mydas) conservation for tourists at Little Liuqiu island, Taiwan: Application of deep learning algorithms - Vincent Y. Chen; Ya-Wen Wu; Chih-Wei Hu; Yu-San Han (Ocean & Coastal Management, 2024)

Effects of erythromycin on biofilm formation and resistance mutation of Escherichia coli on pristine and UV-aged polystyrene microplastics - Xiaofeng Han; Long Fu; Jing Yu; Kunting Li; Ziqing Deng; Ruihao Shu; Dali Wang; Jing You; Eddy Y. Zeng (Water Research, 2024)

Needle and bud scale development in Picea abies - Carol L. Wenzel; Anny Y. Xia; Rebecca Saunders; Han Han Ly; Anson Mo; David M. Holloway (Trees, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Cancellation of resonance for elastically supported beams subjected to successive moving loads: Optimal design condition for bridges - Y.B. Yang; L. Chen; Z.L. Wang; Z.Y. Liu; Ding-Han Liu; H. Yao; Y. Zheng (Engineering Structures, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Deciphering temporal gene expression dynamics in multiple coral species exposed to heat stress: Implications for predicting resilience - Tingyu Han; Xin Liao; Zhuojun Guo; J.-Y. Chen; Chunpeng He; Zuhong Lu (Science of The Total Environment, 2024)

Effectiveness and potential mechanism of hydrothermal modification of attapulgite for cadmium passivation in soil - G. Ma; J. Ren; L. Tao; X. Han; C. Liao; Y. Zhou; J. Ding; Y. Zhou; K. Bi (International Journal of Environmental Science and Technology, 2024)

A bibliometric analysis of the toxicity research of carbon nanomaterials - M. Han; Y. Lei; F. X. Yang; H. F. Sun (International Journal of Environmental Science and Technology, 2024)

Comparison of PM2.5 components and secondary formation during the heavily polluted period of two megacities in China - Z. Ran; X. Wang; X. Yin; Y. Liu; M. Han; Y. Cheng; J. Han; T. Jin (International Journal of Environmental Science and Technology, 2024)

Precisely regulated in-plane pore sizes of Co-MOF nanosheet membranes for efficient dye recovery - Li Wang; Meng Zhang; Yufei Shu; Qi Han; Beizhao Chen; Bei Liu; Zhongying Wang; Chuyang Y. Tang (Desalination, 2023)

Fungal necromass is reduced by intensive drought in subsoil but not in topsoil - Yuwei Liu; Xiaoming Zou; Han Y. H. Chen; Manuel Delgado‐Baquerizo; Cuiting Wang; Chen Zhang; Honghua Ruan (Global Change Biology, 2023)
The frequency and intensity of droughts worldwide are challenging the conservation of soil organic carbon (SOC) pool. Microbial necromass is a key component of SOC, but how it responds to drought at specific soil depths remains largely unknown. Here, we conducted a 3‐year field experiment in a forest plantation to investigate the impacts of drought intensities under three treatments (ambient control [CK], moderate drought [30% throughfall removal], and intensive drought [50% throughfall removal]) on soil microbial necromass pools (i.e., bacterial necromass carbon, fungal necromass carbon, and total microbial necromass carbon). We showed that the effects of drought on microbial necromass depended on microbial groups, soil depth, and drought intensity. While moderate drought increased total (+9.1% ± 3.3%) and fungal (+13.5% ± 4.9%) necromass carbon in the topsoil layer (0–15 cm), intensive drought reduced total (−31.6% ± 3.7%) and fungal (−43.6% ± 4.0%) necromass in the subsoil layer (15–30 cm). In contrast, both drought treatments significantly increased the BNC in the topsoil and subsoil. Our results suggested that the effects of drought on the microbial necromass of the subsoil were more pronounced than those of the topsoil. This study highlights the complex responses of microbial necromass to drought events depending on microbial community structure, drought intensity and soil depth with global implications when forecasting carbon cycling under climate change.

Effects of forest conversion and recovery age on fine root multi-element stoichiometry in subtropical forests - Mingyan Hu; Zilong Ma; Han Y. H. Chen (Plant and Soil, 2023)

Optimization of A2O–MBR–BAF–O3 combination process for domestic wastewater - L. Huang; J. Han; G. Wang; Y. Hou; Z. Li; F. Yi (International Journal of Environmental Science and Technology, 2023)

Biogeographic pattern of living vegetation carbon turnover time in mature forests across continents - Kailiang Yu; Philippe Ciais; Anthony A. Bloom; Jinsong Wang; Zhihua Liu; Han Y. H. Chen; Yilong Wang; Yizhao Chen; Ashley P. Ballantyne (Global Ecology and Biogeography, 2023)
Aim Theoretically, woody biomass turnover time () quantified using outflux (i.e. tree mortality) predicts biomass dynamics better than using influx (i.e. productivity). This study aims at using forest inventory data to empirically test the outflux approach and generate a spatially explicit understanding of woody in mature forests. We further compared woody estimates with dynamic global vegetation models (DGVMs) and with a data assimilation product of C stocks and fluxes—CARDAMOM. Location Continents. Time Period Historic from 1951 to 2018. Major Taxa Studied Trees and forests. Methods We compared the approaches of using outflux versus influx for estimating woody and predicting biomass accumulation rates. We investigated abiotic and biotic drivers of spatial woody and generated a spatially explicit map of woody at a 0.25‐degree resolution across continents using machine learning. We further examined whether six DGVMs and CARDAMOM generally captured the observational pattern of woody . Results Woody quantified by the outflux approach better (with R 2 0.4–0.5) predicted the biomass accumulation rates than the influx approach (with R 2 0.1–0.4) across continents. We found large spatial variations of woody for mature forests, with highest values in temperate forests (98.8 ± 2.6 y) followed by boreal forests (73.9 ± 3.6 y) and tropical forests. The map of woody extrapolated from plot data showed higher values in wetter eastern and pacific coast USA, Africa and eastern Amazon. Climate (temperature and aridity index) and vegetation structure (tree density and forest age) were the dominant drivers of woody across continents. The highest woody in temperate forests was not captured by either DGVMs or CARDAMOM. Main Conclusions Our study empirically demonstrated the preference of using outflux over influx to estimate woody for predicting biomass accumulation rates. The spatially explicit map of woody and the underlying drivers provide valuable information to improve the representation of forest demography and carbon turnover processes in DGVMs.

Functional traits explain waterbirds' host status, subtype richness, and community‐level infection risk for avian influenza - Shenglai Yin; Ning Li; Wenjie Xu; Daniel J. Becker; Willem F. de Boer; Chi Xu; Taej Mundkur; Nicholas M. Fountain‐Jones; Chunlin Li; Guan‐zhu Han; Qiang Wu; Diann J. Prosser; et al. (Ecology Letters, 2023)
Species functional traits can influence pathogen transmission processes, and consequently affect species' host status, pathogen diversity, and community‐level infection risk. We here investigated, for 143 European waterbird species, effects of functional traits on host status and pathogen diversity (subtype richness) for avian influenza virus at species level. We then explored the association between functional diversity and HPAI H5Nx occurrence at the community level for 2016/17 and 2021/22 epidemics in Europe. We found that both host status and subtype richness were shaped by several traits, such as diet guild and dispersal ability, and that the community‐weighted means of these traits were also correlated with community‐level risk of H5Nx occurrence. Moreover, functional divergence was negatively associated with H5Nx occurrence, indicating that functional diversity can reduce infection risk. Our findings highlight the value of integrating trait‐based ecology into the framework of diversity–disease relationship, and provide new insights for HPAI prediction and prevention.

P26-12: Acute and subacute toxicity profiles in Sprague-Dawley (SD) rats treated with Piperis Longi Fructus (PLF) aqueous extract - Y.-B. Kim; W.-J. Im; K.-H. Han (Toxicology Letters, 2023)

P26-11: Acute and subacute toxicity profiles in Sprague-Dawley (SD) rats treated with Piperis Longi Fructus (PLF) Powder - K.-H. Han; W.-J. Im; Y.-B. Kim (Toxicology Letters, 2023)

P24-13: Round Robin Study in Korea on alternative test method for evaluating skin irritation potential of medical devices - J. Yi; Y.S. Park; J.E. Im; H.-W. Moon; J.H. Kim; K.J. Kim; H.S. Yoon; Y. Lee; H.J. Ko; I.S. Kim; J.S. Kim; J.-S. Han; et al. (Toxicology Letters, 2023)

P19-07: 13-week repeated-dose oral toxicity study in rats treated with a mixture of Cirsium japonicum and Brassica oleracea extracts - W.-J. Im; M.-H. Yang; H. Park; J.-S. Han; J.-W. Cho; M.H. Yoo; Y.-B. Kim (Toxicology Letters, 2023)

Petrogenesis and tectonic implications of the early Paleozoic granites in the Lincang granitic batholith, southwestern China: Constraints from geochronology, geochemistry and Hf isotopes - Qian R. Xiao; Qiang Wang; Zhong Y. Liu; Fu H. Xiong; Lei Fan; Han Zhao; Ting T. Gong (Ore and Energy Resource Geology, 2023)

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

NaHCO3 addition enhances water permeance and Ca/haloacetic acids selectivity of nanofiltration membranes for drinking water treatment - Li Long; Lu Elfa Peng; Shenghua Zhou; Qimao Gan; Xianhui Li; Jingyi Jiang; Jiarui Han; Xiangru Zhang; Hao Guo; Chuyang Y. Tang (Water Research, 2023)

Mapping global soil acidification under N deposition - Chen Chen; Wenya Xiao; Han Y. H. Chen (Global Change Biology, 2023)
Soil pH is critically important in regulating soil nutrients and thus influencing the biodiversity and ecosystem functions of terrestrial ecosystems. Despite the ongoing threat of nitrogen (N) pollution especially in the fast‐developing regions, it remains unclear how increasing N deposition affects soil pH across global terrestrial ecosystems. By conducting a global meta‐analysis with paired observations of soil pH under N addition and control from 634 studies spanning major types of terrestrial ecosystems, we show that soil acidification increases rapidly with N addition amount and is most severe in neutral‐pH soils. Grassland soil pH decreases most strongly under high N addition while wetlands are the least acidified. By extrapolating these relationships to global mapping, we reveal that atmospheric N deposition leads to a global average soil pH decline of −0.16 in the past 40 years and regions encompassing Eastern United States, Southern Brazil, Europe, and South and East Asia are the hotspots of soil acidification under N deposition. Our results highlight that anthropogenically amplified atmospheric N deposition has profoundly altered global soil pH and chemistry. They suggest that atmospheric N deposition is a major threat to global terrestrial biodiversity and ecosystem functions.

Paleocurrent and paleowind direction reconstruction research progress and perspectives: a review - F. Y. Zhao; C. L. Hu; C. C. Han; Y. Q. Dong; Q. X. Yuan (Australian Journal of Earth Sciences, 2023)

Spatially explicit estimate of nitrogen effects on soil respiration across the globe - Yang Liu; Mingxin Men; Zhengping Peng; Han Y. H. Chen; Yuanhe Yang; Yunfeng Peng (Global Change Biology, 2023)
Soil respiration (Rs), as the second largest flux of carbon dioxide (CO 2 ) between terrestrial ecosystems and the atmosphere, is vulnerable to global nitrogen (N) enrichment. However, the global distribution of the N effects on Rs remains uncertain. Here, we compiled a new database containing 1282 observations of Rs and its heterotrophic component (Rh) in field N manipulative experiments from 317 published papers. Using this up‐to‐date database, we first performed a formal meta‐analysis to explore the responses of Rs and Rh to N addition, and then presented a global spatially explicit quantification of the N effects using a Random Forest model. Our results showed that experimental N addition significantly increased Rs but had a minimal impact on Rh, not supporting the prevailing view that N enrichment inhibits soil microbial respiration. For the major biomes, the magnitude of N input was the main determinant of the spatial variation in Rs response, while the most important predictors for Rh response were biome specific. Based on the key predictors, global mapping visually demonstrated a positive N effect in the regions with higher anthropogenic N inputs (i.e., atmospheric N deposition and agricultural fertilization). Overall, our analysis not only provides novel insight into the N effects on soil CO 2 fluxes, but also presents a spatially explicit assessment of the N effects at the global scale, which are pivotal for understanding ecosystem carbon dynamics in future scenarios with more frequent anthropogenic activities.

Aquatic photolysis of high-risk chemicals of emerging concern from secondary effluent mediated by sunlight irradiation for ecological safety and the enhanced methods - Danyang Li; Xiaoyan Y. Ma; Shiying Zhang; Yongkun K. Wang; Yingnan Han; Rong Chen; Xiaochang C. Wang; Huu Hao Ngo (Water Research, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

MXene/MnO2 nanocomposite coated superior salt-rejecting biodegradable luffa sponge for efficient solar steam generation - Ahmed Mortuza Saleque; Sainan Ma; Amrit Kumar Thakur; R. Saidur; Tan Kim Han; Mohammad Ismail Hossain; Wayesh Qarony; Y. Ma; Ravishankar Sathyamurthy; Yuen Hong Tsang (Desalination, 2023)

An assessment model for mapping the susceptibility of deposits accumulation on insulators driven by remotely sensed data - G. Wen; G. Han; F. Zhou; L. Shen; Y. Ma; G. Qian; H. Pan; P. Kong; J. Luo (International Journal of Environmental Science and Technology, 2023)

Correction: Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Multi-timescale and control-perceptive scheduling approach for flexible operation of power plant-carbon capture system - Han Xi; Mingjuan Zhu; Kwang Y. Lee; Xiao Wu (Fuel, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Phosphorus additions imbalance terrestrial ecosystem C:N:P stoichiometry - Yuan Sun; Cuiting Wang; Xinli Chen; Shirong Liu; Xingjie Lu; Han Y. H. Chen; Honghua Ruan (Global Change Biology, 2022)
Carbon (C):nitrogen (N):phosphorus (P) stoichiometry in plants, soils, and microbial biomass influences productivity and nutrient cycling in terrestrial ecosystems. Anthropogenic inputs of P to ecosystems are increasing; however, our understanding of the impacts of P addition on terrestrial ecosystem C:N:P ratios remains elusive. By conducting a meta‐analysis with 1413 paired observations from 121 publications, we showed that P addition significantly decreased plant, soil, and microbial biomass N:P and C:P ratios, but had negligible effects on C:N ratios. The reductions in N:P and C:P ratios became more evident as the P application rates and experimental duration increased. The P addition effects on terrestrial ecosystem C:N:P stoichiometry did not vary with ecosystem types or climates. Moreover, the responses of N:P and C:P ratios in soil and microbial biomass were associated with the responses of soil pH and fungi:bacteria ratios. Additionally, P additions increased net primary productivity, microbial biomass, soil respiration, N mineralization, and N nitrification, but decreased ammonium and nitrate contents. Decreases in plant N:P and C:P ratios were both negatively correlated to net primary productivity and soil respiration, but positively correlated to ammonium and nitrate contents; microbial biomass, soil respiration, ammonium contents, and nitrate contents all increased with declining soil N:P and C:P ratios. Our findings highlight that P additions could imbalance C:N:P stoichiometry and potentially impact the terrestrial ecosystem functions.

Characterization and thermal removal of organophosphorus pesticides in soils from a former agrochemical factory - W. Han; Y. Ye; S. Liu; J. Sima (International Journal of Environmental Science and Technology, 2022)

Sustained-release ketamine-loaded lipid-particulate system: in vivo assessment in mice - Weizhi Xu; Faheem Maqbool; Vinod Kumar; James R. Falconer; Cedric S. Cui; Trent M. Woodruff; Karin Borges; Andrew K. Whittaker; Maree T. Smith; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

Using Machine Learning Algorithms for Water Segmentation in Gas Diffusion Layers of Polymer Electrolyte Fuel Cells - Andrew D. Shum; Christopher P. Liu; Wei Han Lim; Dilworth Y. Parkinson; Iryna V. Zenyuk (Transport in Porous Media, 2022)

An Improved Monkey Model of Myocardial Ischemic Infarction for Cardiovascular Drug Development - Keke Wang; Pengfei Han; Lu Huang; Ying Xiao; Jianglong Hou; Pingliang Yang; Yuping Xie; Jindan Cai; Hongge Wang; Y. James Kang (Cardiovascular Toxicology, 2022)

Pore development in terrestrial shale reservoirs: the Permian Lucaogou Formation, Junggar Basin, northwestern China - Y. Jin; J. Tian; C. Han; H. Liu; L. Dong; S. Dan (Australian Journal of Earth Sciences, 2022)

Factors associated with symptoms of poor mental health among women factory workers in China’s supply chain - K. K. Sznajder; S. D. Harlow; J. Wang; L. Tso; Y. Ashagre; C. Han (International Archives of Occupational and Environmental Health, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Mechanical properties and fracture evolution process of Beishan granite under tensile state - C. S. Wang; J. F. Liu; Y. W. Zhao; S. J. Han (Bulletin of Engineering Geology and the Environment, 2022)

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

Advanced research tools for fungal diversity and its impact on forest ecosystem - Muhammad Adnan; Waqar Islam; Liu Gang; Han Y. H. Chen (Environmental Science and Pollution Research, 2022)

Identification and Verification of the Ability of Cdk5 to Phosphorylate Deubiquitinating Enzyme BRCC3 In Vitro - C. H. Zhang; K. Qin; S. L. Tian; Y. Han; S. Y. Xu; X. Y. Shao (Bulletin of Experimental Biology and Medicine, 2022)

Sustained release ketamine-loaded porous silicon-PLGA microparticles prepared by an optimized supercritical CO2 process - Weizhi Xu; Zonglan Zhao; James Falconer; Andrew K. Whittaker; Amirali Popat; Maree T. Smith; Tushar Kumeria; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

Carbon and nitrogen dynamics in tropical ecosystems following fire - Dalong Jiang; Chonghua Xu; Xia Xu; Yiqi Luo; Chen Chen; Chenghui Ju; Han Y. H. Chen; Zheng Shi; Honghua Ruan (Global Ecology and Biogeography, 2022)
Aim Tropical ecosystems have grown increasingly prone to fire over the last century. However, no consensus has yet emerged regarding the effects of fire disturbances on tropical biogeochemical cycles. Location Tropics. Time period 1960–2018. Major taxa studied Tropical ecosystems: Above‐ and below‐ground carbon (C) and nitrogen (N) dynamics. Methods We analysed the impacts of fire on C and N dynamics in tropical ecosystems through a meta‐analysis of 1,420 observations from 87 studies. Results Fire reduced both above‐ and below‐ground C and N pools, with greater reductions above‐ than below‐ground. Fire decreased soil total carbon (TC), total nitrogen (TN) and nitrate nitrogen ( ) and increased ammonium nitrogen ( ) in surface mineral soil layers but did not affect those in deep layers. Fire decreased TC and TN in savanna but did not affect those in tropical dry and moist forests. Fire did not affect and in savanna because of non‐significant responses of N mineralization rate (N min ) to fire. Conversely, fire increased and decreased in tropical dry forest, but did not affect and increased in tropical moist forest owing to thermal decomposition of soil organic N and increased soil nitrification, respectively. Moreover, declined and increased initially and then decreased with time after fire. Above‐ and below‐ground response variables to prescribed fire were mediated largely by fire frequency and experimental duration, respectively. Main conclusions Our results suggest a high vulnerability of the above‐ground C and N pools to fire, whereas the biogeochemical cycles below‐ground are of high complexity. Fire effects on below‐ground C and N pools, which are highly uncertain and vegetation specific, should be investigated further.

Biodiversity alleviates the decrease of grassland multifunctionality under grazing disturbance: A global meta‐analysis - Ruiyang Zhang; Dashuan Tian; Han Y. H. Chen; Eric W. Seabloom; Guodong Han; Shaopeng Wang; Guirui Yu; Zhaolei Li; Shuli Niu (Global Ecology and Biogeography, 2022)
Aim Biodiversity drives the delivery of multiple ecosystem functions related to carbon and nutrient cycling (ecosystem multifunctionality, EMF), and biodiversity and ecosystem functioning are strongly threatened by intensive grazing in grasslands. However, it remains unclear how biodiversity regulates EMF changes in response to intensive grazing. Location Global. Time period From 1992 to 2018. Major taxa studied Grassland. Methods Here, we conducted a global synthesis using 373 paired observations from 90 published studies to address the responses of plant diversity, EMF and their relationships to grazing disturbance depending on grazing intensity, livestock type, grazing duration, and climatic aridity. Results Our results showed that EMF significantly decreased with increasing grazing intensity, but the negative EMF response was alleviated at high levels of plant diversity. The grazing‐induced changes in EMF increased linearly with the changes in plant diversity, with the slopes increasing by 78.9% from light to heavy grazing. In addition, the grazing‐induced decrease of EMF was stronger with longer grazing duration and more arid climates. Structural equation models suggested that grazing intensity reduced EMF largely via decreasing plant diversity, whereas upsizing livestock type promoted EMF by increasing plant diversity. Main conclusions This study highlights the key role of biodiversity in mediating EMF in response to intensifying grazing disturbance. We call for conservation of biodiversity to maintain grassland multifunctionality and services.

Differential DNA Methylation Profiles in Patients with Temporal Lobe Epilepsy and Hippocampal Sclerosis ILAE Type I - Wang Zhang; Haiyang Wang; Binchao Liu; Miaomiao Jiang; Yifei Gu; Shi Yan; Xian Han; Alicia Y. Hou; Chongyang Tang; Zhenfeng Jiang; Hong Shen; Meng Na; et al. (Journal of Molecular Neuroscience, 2021)

Synthesis of a novel ZnFe2O4/porous biochar magnetic composite for Th(IV) adsorption in aqueous solutions - W. D. Wang; Y. X. Cui; L. K. Zhang; Y. M. Li; P. Sun; J. H. Han (International Journal of Environmental Science and Technology, 2021)

Precipitation manipulation and terrestrial carbon cycling: The roles of treatment magnitude, experimental duration and local climate - Jinsong Wang; Dashuan Tian; Alan K. Knapp; Han Y. H. Chen; Yiqi Luo; Zhaolei Li; Enqing Hou; Xinzhao Huang; Lifen Jiang; Shuli Niu (Global Ecology and Biogeography, 2021)
Aim Precipitation manipulation experiments have shown diverse terrestrial carbon (C) cycling responses when the ecosystem is subjected to different magnitudes of altered precipitation, various experimental durations or heterogeneity in local climate. However, how these factors combine to affect C cycle responses to changes in precipitation remains unclear. Location Global. Time period 1990–2019. Major taxa studied Terrestrial ecosystems. Methods Using observations from 230 published studies in which precipitation was manipulated and terrestrial C cycling variables were measured, we conducted a global meta‐analysis to investigate responses of diverse C cycle processes to altered precipitation, including gross ecosystem productivity, ecosystem respiration, net ecosystem productivity, ecosystem carbon use efficiency, net primary productivity (NPP), aboveground and belowground NPP, aboveground and belowground biomass, shoot‐to‐root ratio, soil respiration and soil microbial biomass C. Results We found that C cycling responses were correlated linearly and positively with the magnitude of precipitation treatments. We also detected that the responses of NPP and its aboveground component (ANPP) to altered precipitation weakened with experimental duration. Furthermore, gross ecosystem productivity, ecosystem respiration and net ecosystem productivity showed larger responses to precipitation treatments of greater magnitude over shorter time periods. The response of soil respiration, a key component of the C budget in most terrestrial ecosystems, depended in particular on the local climate. Local temperature and precipitation not only influenced the magnitude of the response of soil respiration to altered precipitation but also affected its sensitivity to the magnitude of the precipitation treatments, with higher sensitivities in the response of soil respiration to treatment magnitude at drier and colder sites. Main conclusions Our findings highlight the importance of the interactions between the magnitude of precipitation treatments, their duration and the local climate in the response of ecosystem C cycling to altered precipitation, which is crucial to a better understanding of ecosystem C processes and functioning and projecting them under changing precipitation regimes.

Correction to: Identification and molecular characterization of tea‑oil camellia‑associated totivirus 1 - Z.-Y. Zhang; H. Huang; X. X. Han; R. Li; L.-P. Wu; L. Wu (Archives of Virology, 2021)

Identification and molecular characterization of tea-oil camellia-associated totivirus 1 - Z.-Y. Zhang; H. Huang; X. X. Han; R. Li; L.-P. Wu; L. Wu (Archives of Virology, 2021)

Asymmetric responses of terrestrial C:N:P stoichiometry to precipitation change - Yuan Sun; Cuiting Wang; Han Y. H. Chen; Xuesong Luo; Nianwei Qiu; Honghua Ruan (Global Ecology and Biogeography, 2021)
Aim The aim was to test whether the responses of C:N:P stoichiometry in plant–soil–microorganism systems to precipitation changes support the prediction of the double asymmetry model, which predicts ecological processes (i.e. aboveground productivity, soil microbial community, and soil respiration) are more sensitive to increased precipitation (R+) than decreased precipitation (R−) under normal precipitation changes, whereas more sensitive to R− than R+ under extreme precipitation changes. Location Global. Time period 1999–2020. Major taxa studied Plants, soils, and soil microorganisms. Methods We performed a global meta‐analysis of 848 observations (587 R− and 261 R+ manipulations) from 160 studies, which tested the effects of precipitation changes on C:N:P across plants, soils, and soil microorganisms. The data encompassed broad variations in ecosystems, climate, precipitation intensity, and experimental duration. Results We revealed that the C:N and C:P ratios of different ecosystem compartments were more sensitive to moderate R+ rather than moderate R−, whereas they exhibited a higher response to extreme R− rather than extreme R+, which supported the prediction of the double asymmetry model. Moreover, such responses were more pronounced under higher precipitation intensities and longer experimental duration. The effects of precipitation changes on the C:N:P stoichiometry of plants, soils, and soil microorganisms were consistent across ecosystem types (i.e. forests and grasslands) and associated background climates (i.e. mean annual temperature and precipitation). Main conclusions Our findings provide the first evidence of the asymmetric responses of C:N:P stoichiometry in above‐ and belowground systems to precipitation change. These results extend the double asymmetric model and improve our understanding of C and N cycling, as well as facilitate the prediction of ecosystem responses to precipitation changes.

Rapid functional shifts across high latitude forests over the last 65 years - Masumi Hisano; Masahiro Ryo; Xinli Chen; Han Y. H. Chen (Global Change Biology, 2021)
Global environmental changes have strongly affected forest demographic rates, particularly amplified tree mortality in high latitude forests (e.g., two to five times greater mortality probability over the half‐century). Although forest functional composition is critical for multitrophic biodiversity and ecosystem functioning, it remains unclear how functional composition has changed over time across large high latitude regions, which have been warming twice the rate of the globe as a whole. Using extensive spatial and long‐term forest inventory data (17,107 plots monitored 1951–2016) across Canada, we found that after accounting for stand age‐dependent functional shifts, functional composition shifted toward fast‐growing deciduous broadleaved trees and higher drought tolerance over time. The temporal shift toward deciduous broadleaved trees was consistent across the baseline climate. However, over the study period, drought tolerance increased (or shade tolerance decreased) by 300% in colder boreal regions, while drought tolerance did not shift significantly in warmer temperate climates. A further analysis accounting for temporal changes in atmospheric CO 2 , temperature, and water availability indicated that the functional composition of colder regions shifted toward drought tolerance more rapidly with rising CO 2 than warmer regions, suggesting the greater vulnerability of boreal forests than temperate forests under ongoing global environmental changes. Future ecosystem management practices should consider spatial differences in functional responses to global environmental change, focusing on high latitude forests experiencing higher rates of warming and compositional changes.

Editorial: Designing a Protocol Adopting an Artificial Intelligence (AI)–Driven Approach for Early Diagnosis of Late-Onset Alzheimer’s Disease - Victor O. K. Li; Jacqueline C. K. Lam; Yang Han; Lawrence Y. L. Cheung; Jocelyn Downey; Tushar Kaistha; Illana Gozes (Journal of Molecular Neuroscience, 2021)

Pseudomonas koreensis promotes tomato growth and shows potential to induce stress tolerance via auxin and polyphenol‐related pathways - Q. Guo; Y. Sun; M. Shi; X. Han; Y. Jing; Y. Li; H. Li; H. Lai (Plant and Soil, 2021)

Application of two-level design method on subway tunnel crossing active fault: a case study on Urumqi subway tunnel intersected by reverse fault dislocation - S. An; L. J. Tao; X. C. Han; Y. Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Global soil microbial biomass decreases with aridity and land‐use intensification - Xiaohua Wan; Xinli Chen; Zhiqun Huang; Han Y. H. Chen (Global Ecology and Biogeography, 2021)
Aim Although global patterns are emerging for the soil total microbial biomass pool, our understanding of the distribution of the finer groups, especially bacterial and fungal biomass, remains limited. Moreover, we lack mechanistic insights into the global variation of soil microbial biomass. Location Global terrestrial ecosystems. Time period 1990–2019. Major taxa studied Bacteria and fungi. Methods By conducting a global synthesis of 4,472 observations from 577 sites published in 404 studies, we examined the global patterns and drivers of the soil total microbial biomass, bacterial and fungal biomass and fungi‐to‐bacteria ratio. Results We found that soil total microbial, bacterial and fungal biomass peaked concurrently in tundras, with lower values in deserts, and that intensification of land use reduced soil total microbial, bacterial and fungal biomass and the fungi‐to‐bacteria biomass ratio. Soil organic carbon was the most important driver for global distribution patterns of both bacterial and fungal biomass. Our structural equation models indicated that soil bacterial and fungal biomass increased with water availability through its positive effect on soil organic carbon on a global scale. In contrast, soil total, bacterial and fungal biomass decreased with mean annual temperature and intensification of land use via their negative effects on soil organic carbon. Main conclusions Our results suggest that decreasing water availability and land‐use intensification could reduce soil microbial biomass and the relative abundance of soil fungi to bacteria, impairing their functions and the services they provide.

Relationships between lognormal distributions of neural properties, activity, criticality, and connectivity - P. A. Robinson; Xiao Gao; Y. Han (Biological Cybernetics, 2021)

Contribution of root traits to variations in soil microbial biomass and community composition - Xiaohua Wan; Xinli Chen; Zhiqun Huang; Han Y. H. Chen (Plant and Soil, 2021)

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

Docosahexaenoic Acid (DHA) Supplementation Alters Phospholipid Species and Lipid Peroxidation Products in Adult Mouse Brain, Heart, and Plasma - Grace Y. Sun; Michael K. Appenteng; Runting Li; Taeseon Woo; Bo Yang; Chao Qin; Meixia Pan; Magdalena Cieślik; Jiankun Cui; Kevin L. Fritsche; Zezong Gu; Matthew Will; et al. (NeuroMolecular Medicine, 2021)

Long‐term, amplified responses of soil organic carbon to nitrogen addition worldwide - Chonghua Xu; Xia Xu; Chenghui Ju; Han Y. H. Chen; Brian J. Wilsey; Yiqi Luo; Wei Fan (Global Change Biology, 2021)
Soil organic carbon (SOC) is the largest carbon sink in terrestrial ecosystems and plays a critical role in mitigating climate change. Increasing reactive nitrogen (N) in ecosystems caused by anthropogenic N input substantially affects SOC dynamics. However, uncertainties remain concerning the effects of N addition on SOC in both organic and mineral soil layers over time at the global scale. Here, we analysed a large empirical data set spanning 60 years across 369 sites worldwide to explore the temporal dynamics of SOC to N addition. We found that N addition significantly increased SOC across the globe by 4.2% (2.7%–5.8%). SOC increases were amplified from short‐ to long‐term N addition durations in both organic and mineral soil layers. The positive effects of N addition on SOC were independent of ecosystem types, mean annual temperature and precipitation. Our findings suggest that SOC increases largely resulted from the enhanced plant C input to soils coupled with reduced C loss from decomposition and amplification was associated with reduced microbial biomass and respiration under long‐term N addition. Our study suggests that N addition will enhance SOC sequestration over time and contribute to future climate change mitigation.

Fatigue-Damage Evolution Characteristics of Interbeded Marble Subjected to Dynamic Uniaxial Cyclic Loads - Y. Wang; S. H. Gao; J. Q. Han (Geotechnical and Geological Engineering, 2021)

Plasma Isolation in a Syringe by Conformal Integration of Inertial Microfluidics - Jung Y. Han; Don L. DeVoe (Annals of Biomedical Engineering, 2021)

Global responses of fine root biomass and traits to plant species mixtures in terrestrial ecosystems - Sai Peng; Han Y. H. Chen (Global Ecology and Biogeography, 2021)
Aim Fine root traits underpin terrestrial ecosystem functioning. Despite ongoing plant diversity loss due to anthropogenic activities, our understanding of the effects of plant diversity on fine root traits remains elusive. We addressed: (a) Do fine roots modify their traits in response to species mixtures? (b) Do these responses change with the species richness in mixtures, stand age, and soil depth? (c) Do plant‐mixture induced responses of root traits differ across terrestrial ecosystems? Location Global. Time period Publication years: 1985–2019. Major taxa studied Plants. Methods We conducted a global meta‐analysis of 852 paired observations from 103 published studies to assess the effects of species mixtures on fine root biomass and traits (including root/shoot ratio, community‐weighted mean rooting depth, root length density, specific root length, mean root diameter and root nitrogen content). Results We found that the effects of species mixtures were highly dependent on species richness in mixtures, stand age, and soil depth. The positive effects of species mixtures on root biomass increased with species richness, soil depth, and mean annual temperature. Species mixture effects on root length density shifted from negative to positive with increasing stand age and soil depth and with decreased temperatures. The effects of species mixtures on specific root length shifted from positive to negative with increasing species richness and soil depth, and from negative to positive with increasing stand age. Main conclusions Our meta‐analysis highlights that the community‐level consequences of changes in plant diversity on fine root traits are not consistent, and that predicting these consequences requires taking into account the extent of changes in plant species richness, stand age, soil depth investigated, background climates, and importantly, particular fine root traits.

Dissociable dopaminergic and pavlovian influences in goal-trackers and sign-trackers on a model of compulsive checking in OCD - D. M. Eagle; C. Schepisi; S. Chugh; S. Desai; S. Y. S. Han; T. Huang; J. J. Lee; C. Sobala; W. Ye; A. L. Milton; T. W. Robbins (Psychopharmacology, 2020)
Rationale Checking is a functional behaviour that provides information to guide behaviour. However, in obsessive-compulsive disorder (OCD), checking may escalate to dysfunctional levels. The processes underpinning the transition from functional to dysfunctional checking are unclear but may be associated with individual differences that support the development of maladaptive behaviour. We examined one such predisposition, sign-tracking to a pavlovian conditioned stimulus, which we previously found associated with dysfunctional checking. How sign-tracking interacts with another treatment with emerging translational validity for OCD-like checking, chronic administration of the dopamine D 2 receptor agonist quinpirole, is unknown. Objectives We tested how functional and dysfunctional checking in the rat observing response task (ORT) was affected by chronic quinpirole administration in non-autoshaped controls and autoshaped animals classified as sign-trackers or goal-trackers. Methods Sign-trackers or goal-trackers were trained on the ORT before the effects of chronic quinpirole administration on checking were assessed. Subsequently, the effects on checking of different behavioural challenges, including reward omission and the use of unpredictable reinforcement schedules, were tested. Results Prior autoshaping increased checking. Sign-trackers and goal-trackers responded differently to quinpirole sensitization, reward omission and reinforcement uncertainty. Sign-trackers showed greater elevations in dysfunctional checking, particularly during uncertainty. By contrast, goal-trackers predominantly increased functional checking responses, possibly in response to reduced discrimination accuracy in the absence of cues signalling which lever was currently active. Conclusions The results are discussed in terms of how pavlovian associations influence behaviour that becomes compulsive in OCD and how this may be dependent on striatal dopamine D 2 receptors.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Geomechanical and Ultrasonic Characteristics of Black Shale During Triaxial Deformation Revealed Using Real-Time Ultrasonic Detection Dependence Upon Bedding Orientation and Confining Pressure - Y. Wang; J. Q. Han (Geotechnical and Geological Engineering, 2020)

Functional and phylogenetic diversity promote litter decomposition across terrestrial ecosystems - Wenya Xiao; Chen Chen; Xinli Chen; Zhiqun Huang; Han Y. H. Chen (Global Ecology and Biogeography, 2020)
Aim Litter decomposition is a vital process of carbon and nutrient cycling in terrestrial ecosystems. Despite rapid declines in plant diversity worldwide, the effects of plant diversity on litter decomposition, along with the factors driving their directions and magnitudes, remain uncertain. Location Global. Time period 1985–2018. Major taxa studied Plants. Methods By synthesizing 492 paired observations of leaf litter mixtures and monocultures from 110 studies, we conducted a global meta‐analysis of the effects of litter mixtures on litter decomposition rates, which were calculated as k coefficients from m t / m 0 = e − kt , where m t was the remaining mass of leaf litter at year t and m 0 was the initial litter mass at the beginning of experiments. Results Litter mixtures on average increased litter decomposition rates by 5.6% (95% confidence intervals, 3.0–8.1%), and the effects of litter mixtures increased with litter species richness, the functional diversity of chemical traits (leaf C, N, P contents and C : N ratio) and phylogenetic diversity consistently across terrestrial ecosystems. The decomposer abundance and function, including soil fauna abundance, microbial biomass, and extracellular enzyme activities, were positively associated with litter mixture effects on decomposition rates. The structural equation models accounted for 48.6% of the global variation in litter decomposition rates and revealed that the positive effects of litter functional diversity on decomposer abundance and function led to increased litter decomposition rates, while litter phylogenetic diversity had a positive direct effect on litter decomposition rates. Main conclusions As indicators for complementarity effects, functional diversity of the chemical traits and phylogenetic diversity lead to more positive litter mixture effects on decomposition. The positive litter diversity effects on decomposition rates are mechanistically linked with soil fauna abundance, microbial biomass, and extracellular enzyme activities. Our results suggest that plant diversity, especially functional and phylogenetic diversity, increases decomposer abundance and function, and thus plays a key role in carbon and nutrient cycling across terrestrial ecosystems.

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Responses of C:N stoichiometry in plants, soil, and microorganisms to nitrogen addition - Yuan Sun; Cuiting Wang; Han Y. H. Chen; Honghua Ruan (Plant and Soil, 2020)

Role of environmental factors in shaping the soil microbiome - Waqar Islam; Ali Noman; Hassan Naveed; Zhiqun Huang; Han Y. H. Chen (Environmental Science and Pollution Research, 2020)

Use of Microfluidics to Fabricate Bioerodable Lipid Hybrid Nanoparticles Containing Hydromorphone or Ketamine for the Relief of Intractable Pain - Minze Zhu; Andrew K. Whittaker; Xingyu Jiang; Rupei Tang; Xuanyu Li; Weizhi Xu; Changkui Fu; Maree T Smith; Felicity Y Han (Pharmaceutical Research, 2020)

Carbon accumulation in agroforestry systems is affected by tree species diversity, age and regional climate: A global meta‐analysis - Zilong Ma; Han Y. H. Chen; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang (Global Ecology and Biogeography, 2020)
Aim Agroforestry is a globally practised system of land use for achieving greater and more diverse biomass production, but it has other ecological benefits, such as mitigation of climate change. Despite this, long‐term carbon (C) accumulation in different components of agroforestry systems, the drivers for C accumulation and the linkages between tree biomass and soil C stocks remain unclear. Location Global. Time period From 1989 to 2019. Major taxa studied Trees. Methods Here, we report on a global meta‐analysis based on 141 studies to identify patterns of C accumulation in tree‐based agroforestry systems compared with sole cropland and pasture. Results We found that agroforestry systems had, on average, 46.1 Mg/ha (95% confidence interval, 36.4–55.8 Mg/ha) more C in tree biomass compared with sole cropland‐ or pasture‐based land uses without trees. Furthermore, agroforestry systems with multiple tree species contained greater biomass C stocks and accumulated biomass C faster than systems with a single tree species. The effect of agroforestry practices on soil C stock increased with tree age, although such increases varied among climatic zones. Agroforestry systems in tropical zones had the ability to increase soil C to peak levels quickly, whereas soil C in temperate zones increased at a slower rate but peaked at a greater overall soil C level. Our structural equation model did not detect a direct linkage between biomass C and changes in total soil C stock in agroforestry systems. Main conclusions Our results demonstrate that planting multiple tree species in agroforestry systems is an important strategy to increase biomass C sequestration, with regional climate affecting the temporal change of soil C in response to agroforestry practices.

2DNEMM: a numerical environmental multimedia modeling method for landfill case study - J Dong; Z Chen; Y Han; J Guo; K Wang (International Journal of Environmental Science and Technology, 2020)

Traits mediate drought effects on wood carbon fluxes - Zhenhong Hu; Han Y. H. Chen; Chao Yue; Xiao Ying Gong; Junjiong Shao; Guiyao Zhou; Jiawei Wang; Minhuang Wang; Jianyang Xia; Yongtao Li; Xuhui Zhou; Sean T. Michaletz (Global Change Biology, 2020)
CO 2 fluxes from wood decomposition represent an important source of carbon from forest ecosystems to the atmosphere, which are determined by both wood traits and climate influencing the metabolic rates of decomposers. Previous studies have quantified the effects of moisture and temperature on wood decomposition, but these effects were not separated from the potential influence of wood traits. Indeed, it is not well understood how traits and climate interact to influence wood CO 2 fluxes. Here, we examined the responses of CO 2 fluxes from dead wood with different traits (angiosperm and gymnosperm) to 0%, 35%, and 70% rainfall reduction across seasonal temperature gradients. Our results showed that drought significantly decreased wood CO 2 fluxes, but its effects varied with both taxonomical group and drought intensity. Drought‐induced reduction in wood CO 2 fluxes was larger in angiosperms than gymnosperms for the 35% rainfall reduction treatment, but there was no significant difference between these groups for the 70% reduction treatment. This is because wood nitrogen density and carbon quality were significantly higher in angiosperms than gymnosperms, yielding a higher moisture sensitivity of wood decomposition. These findings were demonstrated by a significant positive interaction effect between wood nitrogen and moisture on CO 2 fluxes in a structural equation model. Additionally, we ascertained that a constant temperature sensitivity of CO 2 fluxes was independent of wood traits and consistent with previous estimates for extracellular enzyme kinetics. Our results highlight the key role of wood traits in regulating drought responses of wood carbon fluxes. Given that both climate and forest management might extensively modify taxonomic compositions in the future, it is critical for carbon cycle models to account for such interactions between wood traits and climate in driving dynamics of wood decomposition.

Spatial variation in climate modifies effects of functional diversity on biomass dynamics in natural forests across Canada - Masumi Hisano; Han Y. H. Chen (Global Ecology and Biogeography, 2020)
Aim Forest net biomass change (ΔAGB; the difference between biomass gain from growth and loss through mortality) determines how forests contribute to the global carbon cycle. Understanding how plant diversity affects ΔAGB in diverse abiotic conditions is crucial in the face of anthropogenic environmental change. Recent studies have advanced our understanding of the effects of plant diversity on growth dependent on the abiotic context, either supporting or rejecting the stress gradient hypothesis. However, we know little about how diversity influences mortality, which prevents us from knowing how diversity affects ΔAGB in diverse abiotic conditions. Location Across Canada (43–60° N, 52–133° W). Time period 1951–2016. Major taxa studied Ninety‐three tree species. Methods We modelled the relationships of growth, mortality and ΔAGB with functional diversity that represented niche complementarity, while simultaneously accounting for the influence of functional identity and stand age. Results Growth and mortality increased, on average, with functional diversity, but the magnitude of the increase in growth was greater than that of mortality, resulting in an increase of ΔAGB. The positive relationship between growth and functional diversity was more prominent in more humid sites than in drier sites. Mortality increased with functional diversity in drier sites but did not increase in wetter sites. The positive relationship between ΔAGB and functional diversity was strengthened with water availability. Moreover, the positive relationship between growth and functional diversity became stronger with temperature, but the positive associations of diversity with mortality and ΔAGB were consistent across the gradient of temperature. Main conclusions Our results suggest that higher functional diversity leads to an increase in forest biomass accumulation owing to a greater positive effect of functional diversity on productivity than on mortality. However, in contrast to the stress gradient hypothesis, our findings show that the positive effect of functional diversity is more pronounced in an environment favourable for growth.

Variation and evolution of C:N ratio among different organs enable plants to adapt to N‐limited environments - Jiahui Zhang; Nianpeng He; Congcong Liu; Li Xu; Zhi Chen; Ying Li; Ruomeng Wang; Guirui Yu; Wei Sun; Chunwang Xiao; Han Y. H. Chen; Peter B. Reich (Global Change Biology, 2020)
Carbon (C) and nitrogen (N) are the primary elements involved in the growth and development of plants. The C:N ratio is an indicator of nitrogen use efficiency (NUE) and an input parameter for some ecological and ecosystem models. However, knowledge remains limited about the convergent or divergent variation in the C:N ratios among different plant organs (e.g., leaf, branch, trunk, and root) and how evolution and environment affect the coefficient shifts. Using systematic measurements of the leaf–branch–trunk–root of 2,139 species from tropical to cold‐temperate forests, we comprehensively evaluated variation in C:N ratio in different organs in different taxa and forest types. The ratios showed convergence in the direction of change but divergence in the rate of change. Plants evolved toward lower C:N ratios in the leaf and branch, with N playing a more important role than C. The C:N ratio of plant organs (except for the leaf) was constrained by phylogeny, but not strongly. Both the change of C:N during evolution and its spatial variation (lower C:N ratio at midlatitudes) help develop the adaptive growth hypothesis. That is, plants with a higher C:N ratio promote NUE under strong N‐limited conditions to ensure survival priority, whereas plants with a lower C:N ratio under less N‐limited environments benefit growth priority. In nature, larger proportion of species with a high C:N ratio enabled communities to inhabit more N‐limited conditions. Our results provide new insights on the evolution and drivers of C:N ratio among different plant organs, as well as provide a quantitative basis to optimize land surface process models.

The effect of enrichment media on the stimulation of native ureolytic bacteria in calcareous sand - Y.-J. Wang; X.-L. Han; N.-J. Jiang; J. Wang; J. Feng (International Journal of Environmental Science and Technology, 2020)

Reciprocal comparison of geodetically sensed and modeled vertical hydrological loading products - Vagner G. Ferreira; Zhiqiang Liu; Henry C. Montecino; Peng Yuan; Caleb I. Kelly; Abubakar S. Mohammed; Lu Y. Han (Acta Geodaetica et Geophysica, 2020)

Stochastic sediment transport: anomalous diffusions and random movement - Christina W. Tsai; Serena Y. Hung; Tsung-Han Wu (Stochastic Environmental Research and Risk Assessment, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Complementarity effects are strengthened by competition intensity and global environmental change in the central boreal forests of Canada - Eric B. Searle; Han Y. H. Chen (Ecology Letters, 2020)
Increases in niche complementarity have been hypothesised to reduce the intensity of interspecific competition within natural forests. In regions currently experiencing potentially enhanced growth under global environmental change, niche complementarity may become even more beneficial. However, few studies have provided direct evidence of this mechanism. Here, we use data from 180 permanent sample plots in Manitoba, Canada, with a full spatial mapping of all stems, to show that complementarity effects on average increased with neighbourhood competition intensity and temporally rising CO 2 , warming and water availability. Importantly, complementarity effects increased with both shade tolerance and phylogenetic dissimilarity between the focal tree and its neighbours. Our results provide further evidence that increasing stand functional and phylogenetic diversity can improve individual tree productivity, especially for individuals experiencing intense competition and may offer an avenue to maintain productivity under global environmental change.

Consensus Paper: Experimental Neurostimulation of the Cerebellum - Lauren N. Miterko; Kenneth B. Baker; Jaclyn Beckinghausen; Lynley V. Bradnam; Michelle Y. Cheng; Jessica Cooperrider; Mahlon R. DeLong; Simona V. Gornati; Mark Hallett; Detlef H. Heck; Freek E. Hoebeek; Abbas Z. Kouzani; et al. (The Cerebellum, 2019)

Coniferization of the mixed‐wood boreal forests under warm climate - Cécile C. Remy; Dominic Senici; Han Y. H. Chen; Yves Bergeron; Martin Lavoie; Laure Paradis; Adam A. Ali (Journal of Quaternary Science, 2019)
Mixed‐wood boreal forests are characterized by a heterogeneous landscape dominated by coniferous or deciduous species depending on stand moisture and fire activity. Our study highlights the long‐term drivers of these differences between landscapes across mixed‐wood boreal forests to improve simulated vegetation dynamics under predicted climate changes. We investigate the effects of main climate trends and wildfire activities on the vegetation dynamics of two areas characterized by different stand moisture regimes during the last 9000 years. We performed paleofire and pollen analyses in the mixed‐wood boreal forest of north‐western Ontario, derived from lacustrine sediment deposits, to reconstruct historical vegetation dynamics, which encompassed both the Holocene climatic optimum ( ca . 8000–4000 a bp ) and the Neoglacial period ( ca . 4000 a bp ). The past warm and dry period (Holocene climatic optimum) promoted higher fire activity that resulted in an increase in coniferous species abundance in the xeric area. The predicted warmer climate and an increase in drought events should lead to a coniferization of the xeric areas affected by high fire activity while the mesic areas may retain a higher broadleaf abundance, as these areas are not prone to an increase in fire activity. Copyright © 2019 John Wiley & Sons, Ltd.

Rapid Increases in Bat Activity and Diversity after Wetland Construction in an Urban Ecosystem - Kevin A. Parker; Brian T. Springall; Reuben A. Garshong; Ashley N. Malachi; Lauren E. Dorn; Alicia Costa-Terryll; Rachael A. Mathis; Alayna N. Lewis; Cassandra L. MacCheyne; Tronjay T. Davis; Alexis D. Rice; Nyla Y. Varh; et al. (Wetlands, 2019)

Requirements for a Coastal Hazards Observing System - Jérôme Benveniste; Anny Cazenave; Stefano Vignudelli; Luciana Fenoglio-Marc; Rashmi Shah; Rafael Almar; Ole Andersen; Florence Birol; Pascal Bonnefond; Jérôme Bouffard; Francisco Calafat; Estel Cardellach; et al. (Frontiers in Marine Science, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

Species‐rich boreal forests grew more and suffered less mortality than species‐poor forests under the environmental change of the past half‐century - Masumi Hisano; Han Y. H. Chen; Eric B. Searle; Peter B. Reich (Ecology Letters, 2019)
Climate and other global environmental changes are major threats to ecosystem functioning and biodiversity. However, the importance of plant diversity in mitigating the responses of functioning of natural ecosystems to long‐term environmental change remains unclear. Using inventory data of boreal forests of western Canada from 1958 to 2011, we found that aboveground biomass growth increased over time in species‐rich forests but decreased in species‐poor forests, and importantly, aboveground biomass loss from tree mortality was smaller in species‐rich than species‐poor forests. A further analysis indicated that growth of species‐rich (but not species‐poor) forests was statistically positively associated with rising CO 2 , and that mortality in species‐poor forests increased more as climate moisture availability decreased than it did in species‐rich forests. In contrast, growth decreased and mortality increased as the climate warmed regardless of species diversity. Our results suggest that promoting high tree diversity may help reduce the climate and environmental change vulnerability of boreal forests.

Plant diversity loss reduces soil respiration across terrestrial ecosystems - Xinli Chen; Han Y. H. Chen (Global Change Biology, 2019)
The rapid global biodiversity loss has led to the decline in ecosystem function. Despite the critical importance of soil respiration (Rs) in the global carbon and nutrient cycles, how plant diversity loss affects Rs remains uncertain. Here we present a meta‐analysis using 446 paired observations from 95 published studies to evaluate the effects of plant and litter mixtures on Rs and its components. We found that total Rs and heterotrophic respiration (Rh) were, on average, greater in plant mixtures than expected from those of monocultures. These mixture effects increased with increasing species richness (SR) in both plant and litter mixtures. While the positive effects of species mixtures remained similar over time for total Rs, they increased over time for Rh in plant mixtures but decreased in litter mixtures. Despite the wide range of variations in mean annual temperature, annual aridity index, and ecosystem types, the plant mixture effects on total Rs and Rh did not change geographically, except for a more pronounced increase of total Rs in species mixtures with reduced water availability. Our structural equation models suggested that the positive effects of SR and stand age on total and Rh were driven by increased plant inputs and soil microbial biomass. Our results suggest that plant diversity loss has ubiquitous negative impacts on Rs, one of the fundamental carbon‐cycle processes sustaining terrestrial element cycling and ecosystem function.

Identification of phosphorylated proteins in response to salt stress in wheat embryo and endosperm during seed germination - X. Luo; C. Han; X. Deng; D. Zhu; Y. Liu; Y. Yan (Cereal Research Communications, 2019)

Microbes drive global soil nitrogen mineralization and availability - Zhaolei Li; Dashuan Tian; Bingxue Wang; Jinsong Wang; Song Wang; Han Y. H. Chen; Xiaofeng Xu; Changhui Wang; Nianpeng He; Shuli Niu (Global Change Biology, 2019)
Soil net nitrogen mineralization rate (N min ), which is critical for soil nitrogen availability and plant growth, is thought to be primarily controlled by climate and soil physical and/or chemical properties. However, the role of microbes on regulating soil N min has not been evaluated on the global scale. By compiling 1565 observational data points of potential net N min from 198 published studies across terrestrial ecosystems, we found that N min significantly increased with soil microbial biomass, total nitrogen, and mean annual precipitation, but decreased with soil pH. The variation of N min was ascribed predominantly to soil microbial biomass on global and biome scales. Mean annual precipitation, soil pH, and total soil nitrogen significantly influenced N min through soil microbes. The structural equation models ( SEM ) showed that soil substrates were the main factors controlling N min when microbial biomass was excluded. Microbe became the primary driver when it was included in SEM analysis. SEM with soil microbial biomass improved the N min prediction by 19% in comparison with that devoid of soil microbial biomass. The changes in N min contributed the most to global soil NH 4 + ‐N variations in contrast to climate and soil properties. This study reveals the complex interactions of climate, soil properties, and microbes on N min and highlights the importance of soil microbial biomass in determining N min and nitrogen availability across the globe. The findings necessitate accurate representation of microbes in Earth system models to better predict nitrogen cycle under global change.

Global photosynthetic capacity is optimized to the environment - Nicholas G. Smith; Trevor F. Keenan; I. Colin Prentice; Han Wang; Ian J. Wright; Ülo Niinemets; Kristine Y. Crous; Tomas F. Domingues; Rossella Guerrieri; F. Yoko Ishida; Jens Kattge; Eric L. Kruger; et al. (Ecology Letters, 2019)

Detecting hydrological consistency between soil moisture and precipitation and changes of soil moisture in summer over the Tibetan Plateau - X. Meng; R. Li; L. Luan; S. Lyu; T. Zhang; Y. Ao; B. Han; L. Zhao; Y. Ma (Climate Dynamics, 2018)

Optimization of culture medium components and culture period for production of adventitious roots of Echinacea pallida (Nutt.) Nutt - Y. Gao; C. H. Wu; X. C. Piao; L. Han; R. Gao; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

Shifts in functional trait–species abundance relationships over secondary subalpine meadow succession in the Qinghai–Tibetan Plateau - Hui Zhang; Robert John; Shidan Zhu; Hui Liu; Qiuyuan Xu; Wei Qi; Kun Liu; Han Y. H. Chen; Qing Ye (Oecologia, 2018)

Carbon Storage Declines in Old Boreal Forests Irrespective of Succession Pathway - Bilei Gao; Anthony R. Taylor; Eric B. Searle; Praveen Kumar; Zilong Ma; Alexandra M. Hume; Han Y. H. Chen (Ecosystems, 2018)

Shake table tests on RC frame infilled by slitted masonry panels - Terry Y. P. Yuen; Han-hui Zhang; J. S. Kuang; Qunxian Huang (Bulletin of Earthquake Engineering, 2018)

Global effects of plant litter alterations on soil CO 2 to the atmosphere - Xinli Chen; Han Y. H. Chen (Global Change Biology, 2018)
Soil respiration (Rs) is the largest terrestrial carbon (C) efflux to the atmosphere and is predicted to increase drastically through global warming. However, the responses of Rs to global warming are complicated by the fact that terrestrial plant growth and the subsequent input of plant litter to soil are also altered by ongoing climate change and human activities. Despite a number of experiments established in various ecosystems around the world, it remains a challenge to predict the magnitude and direction of changes in Rs and its temperature sensitivity ( Q 10 ) due to litter alteration. We present a meta‐analysis of 100 published studies to examine the responses of Rs and Q 10 to manipulated aboveground and belowground litter alterations. We found that 100% aboveground litter addition (double litter) increased Rs by 26.1% (95% confident intervals, 18.4%–33.7%), whereas 100% aboveground litter removal, root removal and litter + root removal reduced Rs by 22.8% (18.5%–27.1%), 34.1% (27.2%–40.9%) and 43.4% (36.6%–50.2%) respectively. Moreover, the effects of aboveground double litter and litter removal on Rs increased with experimental duration, but not those of root removal. Aboveground litter removal marginally increased Q 10 by 6.2% (0.2%–12.3%) because of the higher temperature sensitivity of stable C substrate than fresh litter. Estimated from the studies that simultaneously tested the responses of Rs to aboveground litter addition and removal and assuming negligible changes in root‐derived Rs, “priming effect” on average accounted for 7.3% (0.6%–14.0%) of Rs and increased over time. Across the global variation in terrestrial ecosystems, the effects of aboveground litter removal, root removal, litter + root removal on Rs as well as the positive effect of litter removal on Q 10 increased with water availability. Our meta‐analysis indicates that priming effects should be considered in predicting Rs to climate change‐induced increases in litterfall. Our analysis also highlights the need to incorporate spatial climate gradient in projecting long‐term Rs responses to litter alterations.

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

Phylogeography of the Asian lesser white-toothed shrew, Crocidura shantungensis, in East Asia: role of the Korean Peninsula as refugium for small mammals - Seo-Jin Lee; Mu-Yeong Lee; Liang-Kong Lin; Y. Kirk Lin; Yuchun Li; E-Hyun Shin; Sang-Hoon Han; Mi-Sook Min; Hang Lee; Kyung Seok Kim (Genetica, 2018)

Study on the performance of the micropile-mechanically stabilized earth wall - Zhi-chao Zhang; Ronald Y. S. Pak; Yu-min Chen; Han-long Liu (Journal of Mountain Science, 2018)

Linking intraspecific trait variability and spatial patterns of subtropical trees - En-Rong Yan; Liu-Li Zhou; Han Y. H. Chen; Xi-Hua Wang; Xiang-Yu Liu (Oecologia, 2018)

Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China - Zaipeng Yu; Minhuang Wang; Zhiqun Huang; Teng‐Chiu Lin; Matthew A. Vadeboncoeur; Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2018)
Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2,736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO 2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations.

Visco-elastic–Plastic Creep Constitutive Relation of Tunnels in Soft Schist - Y. Y. Zuo; L. Han; H. Hu; S. Y. Luo; Y. Zhang; X. M. Chen (Geotechnical and Geological Engineering, 2018)

An Experimental Study of Dependence of Optimum TBM Cutter Spacing on Pre-set Penetration Depth in Sandstone Fragmentation - D. Y. Han; P. Cao; J. Liu; J. B. Zhu (Rock Mechanics and Rock Engineering, 2017)

ccaA and FBP/SBPase Derived From Cyanobacteria Improved Photosynthetic Capacity in Rice - Han Y. Gong; Yang Li; Gen Fang; Dao H. Hu; Zhao H. Wang; Guang H. Yu; Yang S. Li (Plant Molecular Biology Reporter, 2017)

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Removal of Cr(VI) and phenol coupled with the reduction of sulfate by sulfate-reducing bacteria sludge - X. Han; T.-X. Zhou; S.-W. Xu; Y. Li; Y.-F. Wang; Y. Liu (International Journal of Environmental Science and Technology, 2017)

Changes in nutrient concentrations of leaves and roots in response to global change factors - Jordi Sardans; Oriol Grau; Han Y. H. Chen; Ivan A. Janssens; Philippe Ciais; Shilong Piao; Josep Peñuelas (Global Change Biology, 2017)
Global change impacts on biogeochemical cycles have been widely studied, but our understanding of whether the responses of plant elemental composition to global change drivers differ between above‐ and belowground plant organs remains incomplete. We conducted a meta‐analysis of 201 reports including 1,687 observations of studies that have analyzed simultaneously N and P concentrations changes in leaves and roots in the same plants in response to drought, elevated [ CO 2 ], and N and P fertilization around the world, and contrasted the results within those obtained with a general database (838 reports and 14,772 observations) that analyzed the changes in N and P concentrations in leaves and/or roots of plants submitted to the commented global change drivers. At global level, elevated [ CO 2 ] decreased N concentrations in leaves and roots and decreased N:P ratio in roots but no in leaves, but was not related to P concentration changes. However, the response differed among vegetation types. In temperate forests, elevated [ CO 2 ] was related with lower N concentrations in leaves but not in roots, whereas in crops, the contrary patterns were observed. Elevated [ CO 2 ] decreased N concentrations in leaves and roots in tundra plants, whereas not clear relationships were observed in temperate grasslands. However, when elevated [ CO 2 ] and N fertilization coincided, leaves had lower N concentrations, whereas root had higher N concentrations suggesting that more nutrients will be allocated to roots to improve uptake of the soil resources not directly provided by the global change drivers. N fertilization and drought increased foliar and root N concentrations while the effects on P concentrations were less clear. The changes in N and P allocation to leaves and root, especially those occurring in opposite direction between them have the capacity to differentially affect above‐ and belowground ecosystem functions, such as litter mineralization and above‐ and belowground food webs.

Identification of interspecific heterotic loci associated with agronomic traits in rice introgression lines carrying genomic fragments of Oryza glaberrima - Tondi Yacouba Nassirou; Wenchuang He; Caijin Chen; Adedze Y. M. Nevame; Athanase Nsabiyumva; Xilong Dong; Yilong Yin; Quanqin Rao; Wei Zhou; Han Shi; Wubin Zhao; Deming Jin (Euphytica, 2017)

Study on the application of an activator for steel slag powder–cement in muddy soil - Y. K. Wu; X. S. Hu; R. Hu; T. Han; J. L. Yu (European Journal of Environmental and Civil Engineering, 2017)

Metabolites from the co-culture of nigranoic acid and Umbelopsis dimorpha SWUKD3.1410, an endophytic fungus from Kadsura angustifolia - L. Wang; D. Qin; K. Zhang; Q. Huang; S. Liu; M. J. Han; J. Y. Dong (Natural Product Research, 2017)

The Initial Symptom and Motor Progression in Spinocerebellar Ataxias - Lan Luo; Jie Wang; Raymond Y Lo; Karla P Figueroa; Stefan M Pulst; Pei-Hsin Kuo; Susan Perlman; George Wilmot; Christopher M Gomez; Jeremy D. Schmahmann; Henry Paulson; Vikram G Shakkottai; et al. (The Cerebellum, 2017)

The Contribution of Litterfall to Net Primary Production During Secondary Succession in the Boreal Forest - Han Y. H. Chen; Amber N. Brant; Meelis Seedre; Brian W. Brassard; Anthony R. Taylor (Ecosystems, 2017)

Safety Evaluation of Sevoflurane as Anesthetic Agent in Mouse Model of Myocardial Ischemic Infarction - Xiang Cheng; Jianglong Hou; Jiaming Liu; Xiaorong Sun; Qin Sheng; Pengfei Han; Y. James Kang (Cardiovascular Toxicology, 2017)

Response of plant functional traits to species origin and adaptive reproduction in weeds - J. H. Liu; X. H. Yong; Q. Han; A. Ali; Y. J. Wang (Plant Biosystems, 2017)

Sequence variants of the LCORL gene and its association with growth and carcass traits in Qinchuan cattle in China - Y. J. HAN; Y. CHEN; Y. LIU; X. L. LIU (Journal of Genetics, 2017)

Plant invasion is associated with higher plant–soil nutrient concentrations in nutrient‐poor environments - Jordi Sardans; Mireia Bartrons; Olga Margalef; Albert Gargallo‐Garriga; Ivan A. Janssens; Phillipe Ciais; Michael Obersteiner; Bjarni D. Sigurdsson; Han Y. H. Chen; Josep Peñuelas (Global Change Biology, 2017)
Plant invasion is an emerging driver of global change worldwide. We aimed to disentangle its impacts on plant–soil nutrient concentrations. We conducted a meta‐analysis of 215 peer‐reviewed articles and 1233 observations. Invasive plant species had globally higher N and P concentrations in photosynthetic tissues but not in foliar litter, in comparison with their native competitors. Invasive plants were also associated with higher soil C and N stocks and N, P, and K availabilities. The differences in N and P concentrations in photosynthetic tissues and in soil total C and N, soil N, P, and K availabilities between invasive and native species decreased when the environment was richer in nutrient resources. The results thus suggested higher nutrient resorption efficiencies in invasive than in native species in nutrient‐poor environments. There were differences in soil total N concentrations but not in total P concentrations, indicating that the differences associated to invasive plants were related with biological processes, not with geochemical processes. The results suggest that invasiveness is not only a driver of changes in ecosystem species composition but that it is also associated with significant changes in plant–soil elemental composition and stoichiometry.

Persistent and pervasive compositional shifts of western boreal forest plots in Canada - Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2017)
Species compositional shifts have important consequences to biodiversity and ecosystem function and services to humanity. In boreal forests, compositional shifts from late‐successional conifers to early‐successional conifers and deciduous broadleaves have been postulated based on increased fire frequency associated with climate change truncating stand age‐dependent succession. However, little is known about how climate change has affected forest composition in the background between successive catastrophic fires in boreal forests. Using 1797 permanent sample plots from western boreal forests of Canada measured from 1958 to 2013, we show that after accounting for stand age‐dependent succession, the relative abundances of early‐successional deciduous broadleaves and early‐successional conifers have increased at the expense of late‐successional conifers with climate change. These background compositional shifts are persistent temporally, consistent across all forest stand ages and pervasive spatially across the region. Rising atmospheric CO 2 promoted early‐successional conifers and deciduous broadleaves, and warming increased early‐successional conifers at the expense of late‐successional conifers, but compositional shifts were not associated with climate moisture index. Our results emphasize the importance of climate change on background compositional shifts in the boreal forest and suggest further compositional shifts as rising CO 2 and warming will continue in the 21st century.

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

Global estimates of carbon monoxide emissions from 1960 to 2013 - Qirui Zhong; Ye Huang; Huizhong Shen; Yilin Chen; Han Chen; Tianbo Huang; Eddy Y. Zeng; Shu Tao (Environmental Science and Pollution Research, 2017)

Microstructure and Ultrastructure Alterations in the Pallium of Immature Mice Exposed to Cadmium - X. F. Yang; Q. G. Han; D. Y. Liu; H. T. Zhang; G. Y. Fan; J. Y. Ma; Z. L. Wang (Biological Trace Element Research, 2016)

Effects of species diversity on fine root productivity in diverse ecosystems: a global meta‐analysis - Zilong Ma; Han Y. H. Chen (Global Ecology and Biogeography, 2016)
Aim Positive relationships between plant species diversity and above‐ground productivity have been observed across a wide range of terrestrial ecosystems. Despite a critical contribution of below‐ground productivity to overall terrestrial productivity, no consensus exists about the nature of the relationship between species diversity and below‐ground productivity. Location Global. Methods We collected data from published studies conducted in natural and planted forests and experimental grassland, crop and pot systems that were purposely implemented to isolate the effects of plant species diversity from other factors, such as soil conditions and topographic features. We conducted meta‐analyses of 170 observations for root biomass and 23 observations for root production, derived from 48 published studies, using weighted linear modelling with bootstrap procedures to reconcile the effects of diversity on fine root productivity. Results We found that species mixtures had, on average 28.4% higher fine root biomass and 44.8% higher annual production than monocultures. Higher fine root biomass in species mixtures than in monocultures was consistent across natural forests, planted grasslands, croplands and pot systems, except for young planted forests. Transgressive overyielding was only evident for planted grasslands. The log response ratio of fine root biomass in species mixtures to that in respective monocultures increased with species richness across all ecosystem types, and also increased with experiment age in grasslands. Main conclusions Our meta‐analysis reveals positive effects of species diversity on below‐ground productivity. Despite profound differences in environments among terrestrial ecosystems, our analysis demonstrated that below‐ground productivity responds similarly to variations in species richness. Furthermore, our study also reveals shifts in the effects of diversity over time in both forests and grasslands. Future efforts are needed to further understand below‐ground productivity–diversity relationships.

Experimental Investigation on Mechanical Behavior and Permeability Evolution of a Porous Limestone Under Compression - B. Han; S. Y. Xie; J. F. Shao (Rock Mechanics and Rock Engineering, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Synthesis and accumulation of glutenin subunits during grain development in bread wheat as revealed by reversed-phase ultra-performance liquid chromatography (RP-UPLC) - J. Zhou; W. Liu; C. Han; H. Cao; Y. Xu; W. Zhang; Y. Yan (Cereal Research Communications, 2016)

Climate change‐associated trends in net biomass change are age dependent in western boreal forests of Canada - Han Y. H. Chen; Yong Luo; Peter B. Reich; Eric B. Searle; Shekhar R. Biswas (Ecology Letters, 2016)
The impacts of climate change on forest net biomass change are poorly understood but critical for predicting forest's contribution to the global carbon cycle. Recent studies show climate change‐associated net biomass declines in mature forest plots. The representativeness of these plots for regional forests, however, remains uncertain because we lack an assessment of whether climate change impacts differ with forest age. Using data from plots of varying ages from 17 to 210 years, monitored from 1958 to 2011 in western Canada, we found that climate change has little effect on net biomass change in forests ≤ 40 years of age due to increased growth offsetting increased mortality, but has led to large decreases in older forests due to increased mortality accompanying little growth gain. Our analysis highlights the need to incorporate forest age profiles in examining past and projecting future forest responses to climate change.

Phenotypic plasticity controls regional-scale variation in Quercus variabilis leaf δ13C - Xiao Sun; Hongzhang Kang; Han Y. H. Chen; Baoming Du; Shan Yin; Xuan Zhou; Eric B. Searle; Chunjiang Liu (Trees, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

On the stability of colonnade structural systems under static and dynamic loading conditions - V. Sarhosis; P. Asteris; T. Wang; W. Hu; Y. Han (Bulletin of Earthquake Engineering, 2016)

Colored Sticky Traps to Selectively Survey Thrips in Cowpea Ecosystem - L D Tang; H Y Zhao; B L Fu; Y Han; K Liu; J H Wu (Neotropical Entomology, 2016)

Aboveground biomass of understorey vegetation has a negligible or negative association with overstorey tree species diversity in natural forests - Yu Zhang; Han Y. H. Chen; Anthony R. Taylor (Global Ecology and Biogeography, 2016)
Aim The positive relationships between tree species diversity, aboveground biomass and productivity of overstorey tree layers have been widely reported in tropical, temperate and boreal forest ecosystems. However, no consensus has been arrived at on the association between overstorey tree species diversity and the functions of understorey vegetation, such as the biomass of understorey tree, shrub, herb and bryophyte layers, despite their critical contributions to the diversity and functions of natural forests. Location C anadian forest (42°37′ to 68°14′ N ; 53°25′ to 134°46′ W ; 4 to 2170 m elevation). Methods We employed C anada's N ational F orest I nventory dataset to evaluate the influences of overstorey tree species diversity on the aboveground biomass of each forest stratum by accounting for the effects of climate, site condition and stand age. Results We found that aboveground biomass of overstorey trees and total aboveground biomass were positively associated with overstorey tree species richness; however, the aboveground biomass of understorey trees, shrubs, herbs and bryophytes were not associated or were negatively associated with overstorey tree species richness, evenness and life‐history trait variations. Main conclusions Our results show positive associations between aboveground biomass of the overstorey tree layer and overstorey tree species diversity over a wide range of climate, local site conditions and stand ages in natural forests. However, contrary to previous findings that more tree species result in higher levels of multiple ecosystem functions, including understorey plant functions, our results demonstrate that the aboveground biomass of understorey vegetation has either a negligible or negative association with overstorey tree species diversity. The negative associations between overstorey tree species diversity and understorey biomass possibly resulted from greater resource filtering by overstorey trees in ecosystems with more diverse overstorey tree species.

Efficacy of oral moxifloxacin for aerobic vaginitis - C. Wang; C. Han; N. Geng; A. Fan; Y. Wang; Y. Yue; H. Zhang; F. Xue (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Characterization of the disposition of fostamatinib in Japanese subjects including pharmacokinetic assessment in dry blood spots: results from two phase I clinical studies - Paul Martin; S. Y. Amy Cheung; Mark Yen; David Han; Michael Gillen (European Journal of Clinical Pharmacology, 2016)

Cognition and Depression Following Deep Brain Stimulation of the Subthalamic Nucleus and Globus Pallidus Pars Internus in Parkinson’s Disease: A Meta-Analysis - Hannah L. Combs; Bradley S. Folley; David T. R. Berry; Suzanne C. Segerstrom; Dong Y. Han; Amelia J. Anderson-Mooney; Brittany D. Walls; Craig van Horne (Neuropsychology Review, 2015)

Are functional traits a good predictor of global change impacts on tree species abundance dynamics in a subtropical forest? - Ronghua Li; Shidan Zhu; Han Y. H. Chen; Robert John; Guoyi Zhou; Deqiang Zhang; Qianmei Zhang; Qing Ye (Ecology Letters, 2015)
Significant changes in the composition of tree species have been observed in various forests worldwide. We hypothesised that these changes might result from variable sensitivities of species to global change, and species sensitivities might be quantified, using functional traits. Employing long‐term (1978–2010) species abundance data of 48 tree species from a permanent subtropical forest plot, where multiple global change factors have been observed, including soil drying, we examined the relationships between temporal trends in abundance and suits of functional traits. We found that species with high photosynthesis rates, leaf phosphorus and nitrogen concentrations, specific leaf area, hydraulic conductivity, turgor loss point and predawn leaf water potential had increased in abundance, while species with opposite trait patterns had decreased. Our results demonstrate that functional traits underlie tree species abundance dynamics in response to drought stress, thus linking traits to compositional shifts in this subtropical forest under global changes.

Climate change‐associated tree mortality increases without decreasing water availability - Yong Luo; Han Y. H. Chen (Ecology Letters, 2015)
Temporal increases of tree mortality have been observed in regions where global warming has decreased long‐term water availability and/or induced droughts. However, temporal decreases in water availability are not a global phenomenon. Understanding how water deficit‐free forests respond to the recent effects of climate change is paramount towards a full appreciation of the impacts of climate change on global forests. Here, we reveal temporally increasing tree mortality across all study species over the last three decades in the central boreal forests of Canada, where long‐term water availability has increased without apparent climate change‐associated drought. In addition, we find that the effects of conspecific tree‐to‐tree competition have intensified temporally as a mechanism for the increased mortality of shade‐intolerant tree species. Our results suggest that the consequences of climate change on tree mortality are more profound than previously thought.

Net aboveground biomass declines of four major forest types with forest ageing and climate change in western Canada's boreal forests - Han Y. H. Chen; Yong Luo (Global Change Biology, 2015)
Biomass change of the world's forests is critical to the global carbon cycle. Despite storing nearly half of global forest carbon, the boreal biome of diverse forest types and ages is a poorly understood component of the carbon cycle. Using data from 871 permanent plots in the western boreal forest of Canada, we examined net annual aboveground biomass change (Δ AGB ) of four major forest types between 1958 and 2011. We found that Δ AGB was higher for deciduous broadleaf ( DEC ) (1.44 Mg ha −1 year −1 , 95% Bayesian confidence interval ( CI ), 1.22–1.68) and early‐successional coniferous forests ( ESC ) (1.42, CI , 1.30–1.56) than mixed forests ( MIX ) (0.80, CI , 0.50–1.11) and late‐successional coniferous ( LSC ) forests (0.62, CI , 0.39–0.88). Δ AGB declined with forest age as well as calendar year. After accounting for the effects of forest age, Δ AGB declined by 0.035, 0.021, 0.032 and 0.069 Mg ha −1 year −1 per calendar year in DEC , ESC , MIX and LSC forests, respectively. The Δ AGB declines resulted from increased tree mortality and reduced growth in all forest types except DEC , in which a large biomass loss from mortality was accompanied with a small increase in growth. With every degree of annual temperature increase, Δ AGB decreased by 1.00, 0.20, 0.55 and 1.07 Mg ha −1 year −1 in DEC , ESC , MIX and LSC forests, respectively. With every cm decrease of annual climatic moisture availability, Δ AGB decreased 0.030, 0.045 and 0.17 Mg ha −1 year −1 in ESC , MIX and LSC forests, but changed little in DEC forests. Our results suggest that persistent warming and decreasing water availability have profound negative effects on forest biomass in the boreal forests of western Canada. Furthermore, our results indicate that forest responses to climate change are strongly dependent on forest composition with late‐successional coniferous forests being most vulnerable to climate changes in terms of aboveground biomass.

Identification of QTL for adult plant resistance to stripe rust in Chinese wheat landrace Caoxuan 5 - X. L. Zhou; Y. Zhang; Q. D. Zeng; X. M. Chen; D. J. Han; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Application of a high-surface-area schwertmannite in the removal of arsenate and arsenite - J. Song; S.-Y. Jia; H.-T. Ren; S.-H. Wu; X. Han (International Journal of Environmental Science and Technology, 2015)

Sensitivity of Alternaria solani to boscalid and control of boscalid resistance with commonly-used fungicides in Shanxi, China - X. J. Shi; L. Ren; Y. Q. Song; J. C. Han; H. P. Liu; Y. J. Zhang (Australasian Plant Pathology, 2015)

Influence of Constant Temperature on Development and Reproduction of Encarsia guadeloupae Viggiani (Hymenoptera: Aphelinidae), a Parasitoid of the Spiraling Whitefly Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - J Y Chen; L M Niu; L Li; D Y Han; Y G Fu (Neotropical Entomology, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Negative effects of fertilization on plant nutrient resorption - Z. Y. Yuan; Han Y. H. Chen (Ecology, 2015)
Plants in infertile habitats are thought to have a high rate of nutrient resorption to enable them reuse nutrients more efficiently than those in fertile habitats. However, there is still much debate on how plant nutrient resorption responds to nutrient availability. Here we used a meta‐analysis from a global data set of 9703 observations at 306 sites from 508 published articles to examine the effects of nitrogen (N) and phosphorus (P) fertilization on plant foliar N and P concentrations and resorption efficiency. We found that N fertilization enhanced N concentration in green leaves by 27% and P fertilization enhanced green‐leaf P by 73% on average. The N and P concentrations in senesced leaves also increased with respective nutrient fertilization. Resorption efficiencies (percentage of nutrient recovered from senescing leaves) of both N and P declined in response to respective nutrient fertilization. Combined N and P fertilization also had negative effects on both N and P resorption efficiencies. Whether nutrient resorption efficiency differs among plant growth types and among ecosystems, however, remains uncertain due to the limited sample sizes when analyzed by plant growth types or ecosystem types. Our analysis indicates that fertilization decreases plant nutrient resorption and the view that nutrient resorption is a critical nutrient conservation strategy for plants in nutrient‐poor environments cannot be abandoned. The response values to fertilization presented in our analysis can help improve biogeochemical models.

The Effect of Myocardial Infarct Size on Cardiac Reserve in Rhesus Monkeys - Jindan Cai; Xiaorong Sun; Pengfei Han; Ying Xiao; Xin Fan; Yanwen Shang; Y. James Kang (Cardiovascular Toxicology, 2014)

Impact of ubiquitous computing technologies on changing travel and land use patterns - S. H. Lee; Y. T. Leem; J. H. Han (International Journal of Environmental Science and Technology, 2014)

Ecotoxicity of triphenyltin on the marine copepod Tigriopus japonicus at various biological organisations: from molecular to population-level effects - Andy Xianliang Yi; Jeonghoon Han; Jae-Seong Lee; Kenneth M. Y. Leung (Ecotoxicology, 2014)

Recovery of Ecosystem Carbon Stocks in Young Boreal Forests: A Comparison of Harvesting and Wildfire Disturbance - Meelis Seedre; Anthony R. Taylor; Brian W. Brassard; Han Y. H. Chen; Kalev Jõgiste (Ecosystems, 2014)

Decline in Net Ecosystem Productivity Following Canopy Transition to Late-Succession Forests - Anthony R. Taylor; Meelis Seedre; Brian W. Brassard; Han Y. H. Chen (Ecosystems, 2014)

Multiple drivers of plant diversity in forest ecosystems - Yu Zhang; Han Y. H. Chen; Anthony Taylor (Global Ecology and Biogeography, 2014)
Aim Theoretical and empirical studies have shown that climate is a major determinant of species richness, yet the importance of climate relative to local site conditions remains unclear in forest ecosystems across large regions. Furthermore, little is known about how climate and local site conditions affect species evenness and understorey plant diversity. Location Canadian forest (42°37′ to 68°14′ N ; 53°25′ to 134°46′ W ; 4 to 2170 m elevation). Methods Using national, broad‐scale forest inventory data, we tested the influence of growing degree days ( GDD ), climate moisture index ( CMI ), soil drainage class ( SDC ) and stand age ( SA ) on plant diversity across C anada's forests. Diversity was assessed on variable plot sizes from 125 to 500 m 2 for canopy tree and total plant species, and from 100 to 400 m 2 for understorey plants. Results Our models accounted for 47, 30 and 49% of total variation in canopy tree species richness, S impson's dominance index and total plant species richness, respectively. After accounting for the effects of plot size and management history, canopy richness increased with GDD and CMI and peaked at intermediate SDC and SA . Simpson's dominance index decreased with increasing GDD and CMI and was lowest at intermediate SDC and SA . Total species richness was most strongly related to SDC and was highest on imperfectly drained soils. Climatic controls on species richness of understorey strata were generally weaker than those on canopy richness. Main conclusions Our results for canopy richness along a mainly longitudinal gradient demonstrate the positive effects of energy on tree species diversity and show evidence for the effects of local site conditions and secondary succession on diversity. Furthermore, our results show that the extent of the influence of climate and local site conditions on plant species diversity can strongly differ between vegetation strata.

Adsorption of anionic dye on magnesium hydroxide-coated pyrolytic bio-char and reuse by microwave irradiation - X. N. Zhang; G. Y. Mao; Y. B. Jiao; Y. Shang; R. P. Han (International Journal of Environmental Science and Technology, 2014)

Keratinocyte growth factor and thiazolidinediones and linolenic acid differentiate characterized mammary fat pad adipose stem cells isolated from prepubertal Korean black goat to epithelial and adipogenic lineage - A. M. M. T Reza; S. Shiwani; N. K. Singh; J. D. Lohakare; S. J. Lee; D. K. Jeong; J. Y. Han; D. Rengaraj; B. W. Lee (In Vitro Cellular & Developmental Biology - Animal, 2014)

Preliminary Study on the Physiological Characteristics of Transgenic Wheat with Maize C 4 - pepc Gene in Field Conditions - L.L. Han; W.G. Xu; L. Hu; Y. Li; X.L. Qi; J.H. Zhang; H.F. Zhang; Y.X. Wang (Cereal Research Communications, 2014)

Isolation and characterization of two VpYABBY genes from wild Chinese Vitis pseudoreticulata - J. Xiang; R. Q. Liu; T. M. Li; L. J. Han; Y. Zou; T. F. Xu; J. Y. Wei; Y. J. Wang; Y. Xu (Protoplasma, 2013)

Applications of capillary electrophoresis for rapidly separating and characterizing water-soluble proteins of wheat grains - C. Han; Z. Yu; S. Feng; D. Lv; X. Yan; G. Chen; X. Li; W. Ma; Y. Yan (Cereal Research Communications, 2013)

Challenge of weed risk assessment (WRA) for ecological restoration in China: The case of Rhus typhina L. and the new officially released weed risk assessment system - G. M. Wang; J. C. Yang; C. D. Jiang; G. M. Jiang; J. B. Yu; H. B. Shao; G. X. Han; Y. J. Gao (Plant Biosystems, 2013)

Effects of total replacement of dietary fish oil on growth performance and fatty acid compositions of hybrid tilapia (Oreochromis niloticus × O. aureus) - C.-Y. Han; Q.-M. Zheng; L.-N. Feng (Aquaculture International, 2013)

The C‐terminal cysteine of turbot Scophthalmus maximus translationally controlled tumour protein plays a key role in antioxidation and growth‐promoting functions - Z.‐X. Zhang; D.‐Y. Geng; Q. Han; S.‐D. Liang; H.‐R. Guo (Journal of Fish Biology, 2013)
The translationally controlled tumour protein (TCTP) of turbot Scophthalmus maximus ( SmTCTP ) contains only one cysteine (Cys 170 ) at the C‐terminal end. The biological role of this C‐terminal Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP was examined by site‐directed mutation of C170A (Cys 170 →Ala 170 ). It was found that C170A mutation not only obviously decreased the antioxidation capacity of the mutant‐ smtctp ‐transformed bacteria exposed to 0·22 mM hydrogen peroxide, but also significantly interrupted the normal growth and survival of the mutant‐ smtctp ‐transformed bacteria and flounder Paralichthys olivaceus gill ( FG ) cells, indicating a key role played by Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP . This study also suggested that the self‐dimerization or dimerization with other interacting proteins is critical to the growth‐promoting function of SmTCTP .

Numerical study of a new belled wedge pile type under different loading modes - Gang Qiang Kong; Qing Yang; Han Long Liu; Robert Y. Liang (European Journal of Environmental and Civil Engineering, 2013)

Stability of Soil Carbon Stocks Varies with Forest Composition in the Canadian Boreal Biome - Jérôme Laganière; David Paré; Yves Bergeron; Han Y. H. Chen; Brian W. Brassard; Xavier Cavard (Ecosystems, 2013)

Numerical Analysis of Seismic Dynamic Response of Saturated Porous Seabed Around a Buried Pipeline - X. L. Zhang; Y. Han (Marine Georesources & Geotechnology, 2013)

Pathogenesis of type 1 (European genotype) porcine reproductive and respiratory syndrome virus in male gonads of infected boar - K. Han; H. W. Seo; Y. Oh; I. Kang; C. Park; J. H. Han; S.-H. Kim; C. Chae (Veterinary Research Communications, 2013)

Effects of Disturbance on Fine Root Dynamics in the Boreal Forests of Northern Ontario, Canada - Z. Y. Yuan; Han Y. H. Chen (Ecosystems, 2013)

Study of chloropropanols in soy sauce by gas chromatography-triple quadrupole mass spectrometry with coupled column separation without derivatisation - X.-M. Xu; H.-W. Wu; H.-L. He; B.-F. Huang; J.-L. Han; Y.-P. Ren (Food Additives & Contaminants: Part A, 2013)

Comparison of wavelet estimation methods - Bo Y. Yi; Gwang H. Lee; Han-Joon Kim; Hyeong-Tae Jou; Dong G. Yoo; Byong J. Ryu; Keumsuk Lee (Geosciences Journal, 2013)

Erratum to: The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Anne Battisti-Charbonney; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; et al. (Pflügers Archiv - European Journal of Physiology, 2013)

Choice of microsatellite markers for identifying homozygosity of mitotic gynogenetic diploids in Japanese flounder Paralichthys olivaceus - Y. X. Liu; H. Z. Han; Q. L. Wang; L. Jiang; S. L. Wang; X. Y. Zhang; Y. Liu; Y. F. Wang; Y. J. Liu; H. J. Liu (Journal of Fish Biology, 2013)
A set of 72 microsatellite markers distributed evenly among 24 linkage groups were selected from the published genetic linkage maps of Japanese flounder Paralichthys olivaceus . In two normal diploid full‐sib families, the test for Mendelian inheritance showed that genotypic segregation deviations were not significant at all analysed loci. To estimate microsatellite‐centromere map distances, four meiotic gynogenetic diploid lines were produced by the activation of eggs using UV irradiated sperm of red seabream Pagrus major and cold‐shock treatment to block the extrusion of the second polar body. Under the assumption of complete interference, 21 markers were located in the centromeric region, 39 in the telomeric region and the rest in the intermediate region of linkage groups. A total of 192 mitotic gynogenetic diploids from one spawn were identified by these markers. Genotype analysis showed that the number of homozygous individuals decreased as microsatellite‐centromere map distance increased on each linkage group.

Classification of Surface EMGs Using Wavelet Packet Energy Analysis and a Genetic Algorithm-Based Support Vector Machine - Y. Rong; D. Hao; X. Han; Y. Zhang; J. Zhang; Y. Zeng (Neurophysiology, 2013)

Water Maze Spatial Learning Enhances Social Recognition Ability in Aged Rats - Q. Zeng; J. Han; B. Wang; Sh. An; Y. Duan; S. Dong; J. Ma; L. Yang; X. Cao (Neurophysiology, 2012)

Z-Ligustilide Potentiates the Cytotoxicity of Dopamine in Rat Dopaminergic PC12 Cells - Hongyi Qi; Jia Zhao; Yifan Han; Allan S. Y. Lau; Jianhui Rong (Neurotoxicity Research, 2012)

The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; Joseph A. Fisher; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Prolonged exclusive breastfeeding, autumn birth and increased gestational age are associated with lower risk of fever in children with hand, foot, and mouth disease - Q. Zhu; Y. Li; N. Li; Q. Han; Z. Liu; Z. Li; J. Qiu; G. Zhang; F. Li; N. Tian (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Comparative changes in density and demography of large herbivores in the Masai Mara Reserve and its surrounding human-dominated pastoral ranches in Kenya - Nina Bhola; Joseph O. Ogutu; Hans-Peter Piepho; Mohamed Y. Said; Robin S. Reid; N. Thompson Hobbs; Han Olff (Biodiversity and Conservation, 2012)

Isolation and Characterization of a Lytic Myoviridae Bacteriophage PAS-1 with Broad Infectivity in Aeromonas salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; D. H. Kang; C. Oh; S. J. Heo; S. C. Park (Current Microbiology, 2012)

A test of ecological succession hypotheses using 55‐year time‐series data for 361 boreal forest stands - Han Y. H. Chen; Anthony R. Taylor (Global Ecology and Biogeography, 2012)
Aim There has been much work on succession over many decades, but succession fundamentals are still debated because of the reliance on chronosequences and dendrochronological reconstruction, both of which are problematic approaches. Here we use time‐series data to test four hypotheses that lie at the heart of successional theory: (1) the neighbourhood effect hypothesis – tree species abundance is time dependent; (2) the density‐dependence hypothesis – a rare species is more favoured over time; (3) the resource ratio hypothesis – species that can grow at the lowest resource level tend to dominate resource limited sites through succession; and (4) the intermediate disturbance hypothesis – intermediate disturbances increase the abundance of rare species. Location Central boreal forest in Canada (47°50′–50°10′ N; 80°10′–85°50′ W). Methods We used repeated measurements from sequential aerial photography and ground surveys for 361 fire‐origin stands that were measured over a c . 55‐year period. Results Shade‐intolerant Pinus banksiana decreased, tolerant Thuja occidentalis increased, intolerant Populus spp. and Betula papyrifera displayed a U‐shaped trend, and intermediate‐tolerant Picea spp. and tolerant Abies balsamea did not change with time since fire, showing evidence of negative, positive, or neutral neighbourhood effects. Species either persisted for longer or increased more in non‐conspecific stands, and had higher increases in abundance when associated with species of contrasting shade tolerance, supporting the density‐dependence hypothesis and indicating shade‐tolerance complementarity as a mechanism for coexistence. Resource‐poor soils favoured those species capable of tolerating limited resources, whereas rich soils permitted invasion and promoted mixtures, supporting the resource ratio hypothesis. Intermediate disturbances increased the invasibility of rare species. Main conclusions Contrary to previous studies where time since a stand‐replacing disturbance is the sole predictor for succession, our study shows that time alone is either an insufficient predictor or is irrelevant to species dynamics in the boreal forest. Rather, density dependence, site resource and intermediate disturbances are key mechanisms in species dynamics and coexistence over time.

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Starvation reduces the heat shock protein responses in white sturgeon larvae - Dong Han; Susie S. Y. Huang; Wei-Fang Wang; Dong-Fang Deng; Silas S. O. Hung (Environmental Biology of Fishes, 2012)

Complete genomic sequence of a T4-like bacteriophage, phiAS4, infecting Aeromonas salmonicida subsp. salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Electrocardiographic Characterization of Rhesus Monkey Model of Ischemic Myocardial Infarction Induced by Left Anterior Descending Artery Ligation - Pingliang Yang; Pengfei Han; Jianglong Hou; Lizhi Zhang; Haibo Song; Yuping Xie; Yonglin Chen; Huiqi Xie; Fabao Gao; Y. James Kang (Cardiovascular Toxicology, 2011)

Prevalence and different characteristics of two serotypes of Streptococcus parauberis isolated from the farmed olive flounder, Paralichthys olivaceus (Temminck and Schlegel), in Korea - S Y Han; B K Kang; B J Kang; S P Shin; B H Soen; J M Kim; J H Kim; C H Choresca; J E Han; J W Jun; S C Park (Journal of Fish Diseases, 2011)
The prevalence of two serotypes of Streptococcus parauberis isolated from the olive flounder, Paralichthys olivaceus , was evaluated in a total of 29 isolates between 2003 and 2010 in Korea. Streptococcus parauberis isolates were divided into two serologically distinct types (serotype 1 and serotype 2), except for one strain (S1091), using an agglutination assay with rabbit antiserum, and serotype 1 was identified as the dominant type (24 of 29 isolates) in this study. To identify the characteristics of the two serotypes of S. parauberis , we conducted a biochemical test using the API 20 Strep kit, a transmission electron microscopy (TEM) assay, sequence analysis of 16S‐23S rRNA intergenic spacer region (ISR) and a pathogenicity test. In TEM, both serotypes possessed polysaccharide capsule layers around the cell surface when bacterial cells were treated with a homologous serotype of rabbit antiserum. However, we were unable to discriminate serotype‐specific biochemical characteristics and genetic characteristics of 16S‐23S rRNA ISR between the two serotypes. In the pathogenicity test, the serotype 1 strains induced significantly higher mortality than the serotype 2 strains in olive flounder when experimentally inoculated via the intraperitoneal route.

Cardiac Arrhythmias Induced by Chloral Hydrate in Rhesus Monkeys - Pengfei Han; Haibo Song; Pingliang Yang; Huiqi Xie; Y. James Kang (Cardiovascular Toxicology, 2011)

Atypical Aeromonas salmonicida infection in the black rockfish, Sebastes schlegeli Hilgendorf , in Korea - H‐J Han; D‐Y Kim; W‐S Kim; C‐S Kim; S‐J Jung; M‐J Oh; D‐H Kim (Journal of Fish Diseases, 2011)
Cultured black rockfish, Sebastes schlegeli , suffered mass mortalities during winter 2008 and spring 2009 in Korea, showing clinical signs of ulcer lesions and haemorrhages over their body surface. The aetiological agent was identified as Aeromonas salmonicida (strains RFAS‐1, ‐2 and ‐3), which is a non‐pigmented, slow‐growing bacterium. Phenotypes of RFAS strains showed variation, while 16S rRNA, gyrB , rpoD , dnaJ and recA gene sequences of all the strains were affiliated to A. salmonicida. In particular, vapA gene sequences of the strains were most closely related to one of the five subspecies of A. salmonicida subsp. masoucida (=KCCM 40239 T ). LD 50 values of RFAS‐1 for intraperitoneal and intramuscular injection were 1.5 × 10 5.25 and 1.5 × 10 6.4 cfu/rockfish, respectively. However, A. salmonicida strains KCCM 40239 T and SAS‐1, which originate from masou and chum salmon, respectively, were not pathogenic to black rockfish. RFAS strains, possessing A‐layer protein on their surface, exhibited β‐haemolytic activity against rockfish erythrocytes and capability to survive in rockfish serum, which seem to be associated with virulence.

A Matched Asymptotic Expansion Analysis of Highly Unsteady Porous Media Flows - S. Y. Han; D. Hansen; G. C. Kember (Transport in Porous Media, 2010)

Spatiotemporal Variations of Fire Frequency in Central Boreal Forest - Dominic Senici; Han Y. H. Chen; Yves Bergeron; Dominic Cyr (Ecosystems, 2010)

A Nonlinear Thin-Wall Model for Vein Buckling - Avione Y. Lee; Hai-Chao Han (Cardiovascular Engineering and Technology, 2010)

Effects of stand age, wildfire and clearcut harvesting on forest floor in boreal mixedwood forests - Bharat M. Shrestha; Han Y. H. Chen (Plant and Soil, 2010)

Evaluation of Ocean Tide Models Used for Jason-2 Altimetry Corrections - H. S. Fok; H. Baki Iz; C. K. Shum; Yuchan Yi; Ole Andersen; Alexander Braun; Yi Chao; Guoqi Han; C. Y. Kuo; Koji Matsumoto; Y. Tony Song (Marine Geodesy, 2010)

Determination of Imazaquin and its Metabolite by Liquid Chromatography-Quadrupole-Time of Flight Tandem Mass - H. B. Yao; G. J. Han; G. X. Liu; Y. Xie; C. H. Wang (Bulletin of Environmental Contamination and Toxicology, 2010)

Does larval duration contribute to population genetic isolation of the Japanese eel Anguilla japonica ? - Y. S. HAN; C. L. HUNG; Y. IIZUKA; H. C. CHANG; B. J. CHANG; H. C. HO; J. C. SHIAO (Fisheries Management and Ecology, 2010)

Is understory plant species diversity driven by resource quantity or resource heterogeneity? - Samuel F. Bartels; Han Y. H. Chen (Ecology, 2010)
What maintains plant species diversity has been the subject of much debate with no general consensus. In forest ecosystems in which understory plants account for the majority of floristic diversity, a crucial question is whether understory plant diversity is driven by resource quantity or resource heterogeneity. This study sought to reconcile the two hypotheses in relation to their effects on understory plant diversity in forest ecosystems. A database of studies that investigated the effects of resources on understory plant diversity was compiled and analyzed using log‐linear models. Whether resource quantity or resource heterogeneity is the determinant of understory plant diversity in individual studies was dependent on stand successional stage(s), presence or absence of intermediate disturbance, and forest biome within which the studies were conducted. Resource quantity was found to govern species diversity in both young and mature stands, whereas resource heterogeneity dominated in old‐growth stands. Resource quantity remained the important driver in both disturbed and undisturbed forests, but resource heterogeneity played an important role in disturbed forests. We argue that neither resource quantity nor heterogeneity alone structures species diversity in forest ecosystems, but rather their influences on understory plant diversity vary with stand development and disturbances in forest ecosystems.

Human Enteric Viruses in Groundwater - S. H. Park; E. J. Kim; T. H. Yun; J. H. Lee; C. K. Kim; Y. H. Seo; S. A. Oh; S. S. Choi; S. J. Cho; M. S. Kim; G. Y. Han; M. Y. Kim; et al. (Food and Environmental Virology, 2010)

Population structure of the olive flounder ( Paralichthys olivaceus ) in Korea inferred from microsatellite marker analysis - W.‐J. Kim; K.‐K. Kim; H.‐S. Han; B.‐H. Nam; Y.‐O. Kim; H.‐J. Kong; J.‐K. Noh; M. Yoon (Journal of Fish Biology, 2010)
The population structure of olive flounder Paralichthys olivaceus was estimated using nine polymorphic microsatellite (MS) loci in 459 individuals collected from eight populations, including five wild and three hatchery populations in Korea. Genetic variation in hatchery (mean number of alleles per locus, A = 10·2–12·1; allelic richness, A R = 9·3–10·1; observed heterozygosity, H O = 0·766–0·805) and wild (mean number of alleles per locus, A = 11·8–19·6; allelic richness, A R = 10·9–16·1; observed heterozygosity, H O = 0·820–0·888) samples did not differ significantly, suggesting a sufficient level of genetic variation in these well‐managed hatchery populations, which have not lost a substantial amount of genetic diversity. Neighbour‐joining tree and principal component analyses showed that genetic separation between eastern and pooled western and southern wild populations in Korea was probably influenced by restricted gene flow between regional populations due to the barrier effects of sea currents. The pooled western and southern populations are genetically close, perhaps because larval dispersal may depend on warm currents. One wild population (sample from Wando) was genetically divergent from the main distribution, but it was genetically close to hatchery populations, indicating that the genetic composition of the studied populations may be affected by hydrographic conditions and the release of fish stocks. The estimated genetic population structure and potential applications of MS markers may aid in the proper management of P. olivaceus populations.

Comparison of reproductive development in triploid and diploid female rainbow trout Oncorhynchus mykiss - Y. Han; M. Liu; L. Lan Zhang; B. Simpson; G. Xue Zhang (Journal of Fish Biology, 2010)
The diploid rainbow trout Oncorhynchus mykiss reached sexual maturity 3 years after hatching and its oogenesis underwent four stages, which were oogonia, primary oocyte, secondary oocyte and egg. Reproductive development and hormone changes of 4 to 35 month‐old female O. mykiss were investigated using histological and radioimmunoassay methods in order to provide a theoretical and practical basis for the use of triploid female O. mykiss . The oogonium of the triploid female could develop into the oocytes of the prophase with abortion occurring later; the oogonium was surrounded by stroma cells to form the oogonium cluster and the gonads showed a virilescent tendency when the oogonium clusters were gradually replaced by spermatogenic‐like cytocysts. After 13 months, amounts of gonadotropic hormone (GtH‐I, GtH‐II) and oestradiol (17 β ‐E 2 ) in triploid females were lower than in diploid fish at corresponding time periods, but the amounts of testosterone (T) increased consistently after 21 months and were more than in diploid fish in the corresponding time periods ( P > 0·05). The infertility of triploid females resulted from meiosis failure, which caused developmental abortion of oocytes and oogonium formed cytocysts before the prophase oocytes. The cytocyst formation was due to the lack of the normal interaction of ovum and follicular cells, the development of follicular cells producing steroids were inhibited, the arylate path from T to 17 β ‐E 2 was interrupted, concentration of 17 β ‐E 2 decreased and concentration of T increased in the blood, the content of vitellogenin (Vg) decreased in the liver with a low 17 β ‐E 2 and high T caused to ovaries to show a tendency to be virilescent.

Effect of paraquat on the antioxidative enzyme activities and lipid peroxidation in opium poppy (Papaver somniferum L.) - R. Zhao; P. -Y. Guo; X. -Y. Yuan; J. -Y. Wang; M. -Q. Han (Journal of Plant Diseases and Protection, 2010)

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken - R. L. Han; X. Y. Lan; L. Z. Zhang; G. Ren; Y. J. Jing; M. J. Li; B. Zhang; M. Zhao; Y. K. Guo; X. T. Kang; H. Chen (Journal of Applied Genetics, 2010)

Magnetic propulsion of a magnetic device using three square-Helmholtz coils and a square-Maxwell coil - Yong H. Ha; Byung H. Han; Soo Y. Lee (Medical & Biological Engineering & Computing, 2010)

Application of an Improved Flow-Stress-Damage Model to the Criticality Assessment of Water Inrush in a Mine: a Case Study - H. Q. Zhang; Y. N. He; C. A. Tang; Bashir Ahmad; L. J. Han (Rock Mechanics and Rock Engineering, 2009)

Characterization of chikusaku-eki and mokusaku-eki and its inhibitory effect on sapstaining fungal growth in laboratory scale - N. Velmurugan; S. S. Chun; S. S. Han; Y. S. Lee (International Journal of Environmental Science and Technology, 2009)

Estimated PBDE and PBB Congeners in Soil from an Electronics Waste Disposal Site - H.-M. Wang; Y.-J. Yu; M. Han; S.-W. Yang; Q. li; Y. Yang (Bulletin of Environmental Contamination and Toxicology, 2009)

Molecular characterization of hepatitis A virus isolated from acute gastroenteritis patients in the Seoul region of Korea - S.-H. Park; E.-J. Kim; J.-H. Lee; S.-S. Choi; M.-S. Kim; S.-S. Jung; G.-Y. Han; H.-S. Yun; D.-S. Chun; S.-S. Oh; H.-S. Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Global trends in senesced‐leaf nitrogen and phosphorus - Zhiyou Yuan; Han Y. H. Chen (Global Ecology and Biogeography, 2009)
Aim Senesced‐leaf litter plays an important role in the functioning of terrestrial ecosystems. While green‐leaf nutrients have been reported to be affected by climatic factors at the global scale, the global patterns of senesced‐leaf nutrients are not well understood. Location Global. Methods Here, bringing together a global dataset of senesced‐leaf N and P spanning 1253 observations and 638 plant species at 365 sites and of associated mean climatic indices, we describe the world‐wide trends in senesced‐leaf N and P and their stoichiometric ratios. Results Concentration of senesced‐leaf N was highest in tropical forests, intermediate in boreal, temperate, and mediterranean forests and grasslands, and lowest in tundra, whereas P concentration was highest in grasslands, lowest in tropical forests and intermediate in other ecosystems. Tropical forests had the highest N : P and C : P ratios in senesced leaves. When all data were pooled, N concentration significantly increased, but senesced‐leaf P concentration decreased with increasing mean annual temperature (MAT) and mean annual precipitation (MAP). The N : P and C : P ratios also increased with MAT and MAP, but C : N ratios decreased. Plant functional type (PFT), i.e. life‐form (grass, herb, shrub or tree), phylogeny (angiosperm versus gymnosperm) and leaf habit (deciduous versus evergreen), affected senesced‐leaf N, P, N : P, C : N and C : P with a ranking of senesced‐leaf N from high to low: forbs ≈ shrubs ≈ trees > grasses, while the ranking of P was forbs ≈ shrubs ≈ trees Main conclusions Globally, senesced‐leaf N and P concentrations differed among ecosystem types, from tropical forest to tundra. Differences were significantly related to global climate variables such as MAT and MAP and also related to plant functional types. These results at the global scale suggest that nutrient feedback to soil through leaf senescence depends on both the climatic conditions and the plant composition of an ecosystem.

Response of Six Boreal Tree Species to Stand Replacing Fire and Clearcutting - Triin Ilisson; Han Y. H. Chen (Ecosystems, 2009)

Analysis of genetic structure and relationship among nine indigenous Chinese chicken populations by the Structure program - H. F. Li; W. Han; Y. F. Zhu; J. T. Shu; X. Y. Zhang; K. W. Chen (Journal of Genetics, 2009)

Embryogenic tissue initiation and somatic embryogenesis in Fraser fir (Abies fraseir [Pursh] Poir.) - Y. W. Kim; R. Newton; J. Frampton; K.-H. Han (In Vitro Cellular & Developmental Biology - Plant, 2009)

A Review of Forest Succession Models and Their Suitability for Forest Management Planning - Anthony R. Taylor; Han Y. H. Chen; Laird VanDamme (Forest Science, 2009)
Successful implementation of ecosystem management requires strategic forest management planning, including the ability to forecast future forest composition. With advances in ecological modeling, many forms of succession models are available. In this review, we provide a broad synthesis of the methods used to model forest succession and discuss their suitability for strategic forest management planning. Qualitative models underpin theoretical understanding of forest succession but require expression in more formal quantitative forms to be applicable to strategic planning. Quantitative modeling methods can be differentiated as empirical or mechanistic. Empirical models rely on observational data of successional change. Mechanistic models rely on knowledge of underlying ecological processes to simulate succession. Hybrid mechanistic models represent a compromise in ecological modeling between empirical robustness and theoretical understanding. With their increased flexibility for scenario planning and enhanced representation of ecosystem processes, hybrid models are well suited to addressing the multiple environmental and social factors increasingly being considered under ecosystem management. However, empirical models still remain a suitable and practical alternative because hybrid models require increased resources to initialize, operate, and interpret; emphasize understanding rather than prediction; and assume that the modeled processes they represent are adequately understood.

An Evaluation of Four Phylogenetic Markers in Nostoc: Implications for Cyanobacterial Phylogenetic Studies at the Intrageneric Level - D. Han; Y. Fan; Z. Hu (Current Microbiology, 2009)

Global‐scale patterns of nutrient resorption associated with latitude, temperature and precipitation - Z. Y. Yuan; Han Y. H. Chen (Global Ecology and Biogeography, 2009)
Aim Nutrient resorption from senescing leaves is an important mechanism of nutrient conservation in plants, but the patterns of nutrient resorption at the global scale are unknown. Because soil nutrients vary along climatic gradients, we hypothesize that nutrient resorption changes with latitude, temperature and precipitation. Location Global. Methods We conducted a meta‐analysis on a global data set collected from published literature on nitrogen (N) and phosphorus (P) resorption of woody plants. Results For all data pooled, both N resorption efficiency (NRE) and P resorption efficiency (PRE) were significantly related to latitude, mean annual temperature (MAT) and mean annual precipitation (MAP): NRE increased with latitude but decreased with MAT and MAP. In contrast, PRE decreased with latitude but increased with MAT and MAP. When functional groups (shrub versus tree, coniferous versus broadleaf and evergreen versus deciduous) were examined individually, the patterns of NRE and PRE in relation to latitude, MAT and MAP were generally similar. Main conclusions The relationships between N and P resorption and latitude, MAT and MAP indicate the existence of geographical patterns of plant nutrient conservation strategies in relation to temperature and precipitation at the global scale, particularly for PRE, which can be an indicator for P limitation in the tropics and selective pressure shaping the evolution of plant traits. Our results suggest that, although the magnitude of plant nutrient resorption might be regulated by local factors such as substrate, spatial patterns are also controlled by temperature or precipitation.

Establishing the foundation for an applied molecular taxonomy of otters in Southeast Asia - Klaus-Peter Koepfli; Budsabong Kanchanasaka; Hiroshi Sasaki; Hélène Jacques; Kristina D. Y. Louie; Toanvong Hoai; Nguyen Xuan Dang; Eli Geffen; Arno Gutleb; Sung-yong Han; Thrine M. Heggberget; Lionel LaFontaine; et al. (Conservation Genetics, 2008)

Neural network determination of cloud attenuation to estimate insolation using MTSAT‐1R data - J.‐M. Yeom; K.‐S. Han; Y.‐S. Kim; J.‐D. Jang (International Journal of Remote Sensing, 2008)

Ivermectin inhibits LPS-induced production of inflammatory cytokines and improves LPS-induced survival in mice - X. Zhang; Y. Song; X. Ci; N. An; Y. Ju; H. Li; X. Wang; C. Han; J. Cui; X. Deng (Inflammation Research, 2008)

Effects of Forest Type and Disturbance on Diversity of Coarse Woody Debris in Boreal Forest - Brian W. Brassard; Han Y. H. Chen (Ecosystems, 2008)

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

Sources and Properties of Natural Organic Matter (NOM) in Water Along the Dongjiang River (the Source of Hong Kong’s Drinking Water) and Toxicological Assay of Its Chlorination By-Products - Y. Liang; H. C. Hong; L. H. Dong; C. Y. Lan; B. P. Han; M. H. Wong (Archives of Environmental Contamination and Toxicology, 2008)

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Changes in Chlorophyll Fluorescence in Maize Plants with Imposed Rapid Dehydration at Different Leaf Ages - Z. Z. Xu; G. S. Zhou; Y. L. Wang; G. X. Han; Y. J. Li (Journal of Plant Growth Regulation, 2008)

Characterization of a Homogentisate Dioxygenase Mutant in Pseudomonas chlororaphis O6 - B. R. Kang; S. H. Han; S. M. Cho; A. J. Anderson; I. S. Kim; S. K. Park; Y. C. Kim (Current Microbiology, 2008)

Genotypic differences in leaf biochemical, physiological and growth responses to ozone in 20 winter wheat cultivars released over the past 60 years - D. K. BISWAS; H. XU; Y. G. LI; J. Z. SUN; X. Z. WANG; X. G. HAN; G. M. JIANG (Global Change Biology, 2008)
Ozone (O 3 ) concentrations in periurban areas in East Asia are sufficiently high to decrease crop yield. However, little is known about the genotypic differences in O 3 sensitivity in winter wheat in relation to year of cultivar release. This paper reports genotypic variations in O 3 sensitivity in 20 winter wheat cultivars released over the past 60 years in China highlighting O 3 ‐induced mechanisms. Wheat plants were exposed to elevated O 3 (82 ppb O 3 , 7 h day −1 ) or charcoal‐filtered air ( 3 ) for 21 days in open top chambers. Responses to O 3 were assessed by the levels of antioxidative activities, protein alteration, membrane lipid peroxidation, gas exchange, leaf chlorophyll, dark respiration and growth. We found that O 3 significantly reduced foliar ascorbate (−14%) and soluble protein (−22%), but increased peroxidase activity (+46%) and malondialdehyde (+38%). Elevated O 3 depressed light saturated net photosynthetic rate (−24%), stomatal conductance (−8%) and total chlorophyll (−11%), while stimulated dark respiration (+28%) and intercellular CO 2 concentration (+39%). O 3 also reduced overall plant growth, but to a greater extent in root (−32%) than in shoot (−17%) biomass. There was significant genotypic variation in potential sensitivity to O 3 that did not correlate to observed O 3 tolerance. Sensitivity to O 3 in cultivars of winter wheat progressed with year of release and correlated with stomatal conductance and dark respiration in O 3 ‐exposed plants. O 3 ‐induced loss in photosynthetic rate was attributed primarily to impaired activity of mesophyll cells and loss of integrity of cellular membrane as evidenced by increased intercellular CO 2 concentration and lipid peroxidation. Our findings demonstrated that higher sensitivity to O 3 in the more recently released cultivars was induced by higher stomatal conductance, larger reduction in antioxidative capacity and lower levels of dark respiration leading to higher oxidative damage to proteins and integrity of cellular membranes.

A novel gene, Pi40(t), linked to the DNA markers derived from NBS-LRR motifs confers broad spectrum of blast resistance in rice - J. U. Jeung; B. R. Kim; Y. C. Cho; S. S. Han; H. P. Moon; Y. T. Lee; K. K. Jena (Theoretical and Applied Genetics, 2007)

Monitoring of Aerial Pollutants Emitted from Swine Houses in Korea - Ki Y. Kim; Han J. Ko; Hyeon T. Kim; Yoon S. Kim; Young M. Roh; Cheol M. Lee; Chi N. Kim (Environmental Monitoring and Assessment, 2007)

Redirecting retroviral tropism by insertion of hepatitis B virus PreS1 core peptide into the envelope - P. Qi; J.-X. Han; Y.-Q. Lu; C.-X. Wang (Archives of Virology, 2007)

Surveying sandy deserts and desertified lands in north‐western China by remote sensing - C. Z. Yan; T. Wang; Z. W. Han; Y. F. Qie (International Journal of Remote Sensing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cross-bridge kinetics of fast and slow fibres of cat jaw and limb muscles: correlations with myosin subunit composition - Joseph F. Y. Hoh; Zhao-Bo Li; Han Qin; Michael K. H. Hsu; Gunther H. Rossmanith (Journal of Muscle Research and Cell Motility, 2007)

Effect of Cadmium in Feed on Organs and Meat Colour of Growing Pigs - Y.-J. Tu; X.-Y. Han; Z.-R. Xu; Y.-Z. Wang; W.-F. Li (Veterinary Research Communications, 2007)

Effects of boundary-layer stability on urban heat island-induced circulation - J.-J. Baik; Y.-H. Kim; J.-J. Kim; J.-Y. Han (Theoretical and Applied Climatology, 2007)

Spectral reflectance and leaf internal structure changes of barley plants due to phytoextraction of zinc and cadmium - B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Monitoring the effects of arsenic and chromium accumulation in Chinese brake fern ( Pteris vittata ) - Maruthi B. B. Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Spatial analysis for spring bloom and nutrient limitation in Xiangxi bay of three Gorges Reservoir - L. Ye; X. Q. Han; Y. Y. Xu; Q. H. Cai (Environmental Monitoring and Assessment, 2007)

Approaching chickpea quantitative trait loci conditioning resistance to Ascochyta rabiei via comparative genomics - X. Y. Bian; R. Ford; T. R. Han; T. E. Coram; E. C. K. Pang; P. W. J. Taylor (Australasian Plant Pathology, 2007)

Pacemaker currents modulated by C-type natriuretic peptide in interstitial cells of Cajal from murine small intestine - Y. Zhang; L. Hua Piao; X. Huang; Y. Fei Han; P. Zhao; L. Gao; Y. Kim; W. X. Xu (Journal of Physiology and Biochemistry, 2006)

Removal of Alachlor and Pretilachlor by Laboratory-Synthesized Zerovalent Iron in Pesticide Formulation Solution - H. Y. Kim; I. K. Kim; J. H. Shim; Y.-C. Kim; T.-H. Han; K.-C. Chung; P. I. Kim; B.-T. Oh; I. S. Kim (Bulletin of Environmental Contamination and Toxicology, 2006)

Soil Nitrification and Denitrification Potentials in a Wheat Field Soil as Affected by Elevated Atmospheric CO2 and Rice Straw Incorporation - Y. Shi; S. Y. Wang; L. Han; J. Yue; L. X. Yang; Y. L. Wang; J. G. Zhu (Bulletin of Environmental Contamination and Toxicology, 2006)

A novel deletion in TNNI2 causes distal arthrogryposis in a large Chinese family with marked variability of expression - Miao Jiang; Xiuli Zhao; Weitian Han; Chaoying Bian; Xuefu Li; Ge Wang; Yang Ao; Yunqing Li; Dongxu Yi; Yang Zhe; Wilson H. Y. Lo; Xue Zhang; et al. (Human Genetics, 2006)

Detection and identification of avian, duck, and goose reoviruses by RT-PCR: goose and duck reoviruses are part of the same genogroup in the genus Orthoreovirus - Y. Zhang; M. Liu; O. Shuidong; Q. L. Hu; D. C. Guo; H. Y. Chen; Z. Han (Archives of Virology, 2006)

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Genetic diversity of avian infectious bronchitis coronavirus strains isolated in China between 1995 and 2004 - S. W. Liu; Q. X. Zhang; J. D. Chen; Z. X. Han; X. Liu; L. Feng; Y. H. Shao; J. G. Rong; X. G. Kong; G. Z. Tong (Archives of Virology, 2006)

N-acetylphytosphingosine-induced apoptosis of Jurkat cells is mediated by the conformational change in Bak - Y. Han; Y. Kim; H. Kang; S. H. Hong; Y. H. Kim; D. -S. Lim; C. Park; Y. -S. Yun; J. -Y. Song (Apoptosis, 2006)

Post-harvest Regeneration of Lowland Black Spruce Forests in Northeastern Ontario - Han Y. H. Chen; Jian R. Wang (New Forests, 2006)

Pioglitazone, a synthetic ligand for PPARγ, induces apoptosis in RB-deficient human colorectal cancer cells - C. J. Lee; J. S. Han; C. Y. Seo; T. H. Park; H. C. Kwon; J. S. Jeong; I. H. Kim; J. Yun; Y. S. Bae; J. Y. Kwak; J. I. Park (Apoptosis, 2006)

Interactions Between High pH and Iron Supply on Nodulation and Iron Nutrition of Lupinus albus L. Genotypes Differing in Sensitivity to Iron Deficiency - C. Tang; S. J. Zheng; Y. F. Qiao; G. H. Wang; X. Z. Han (Plant and Soil, 2006)

Radon distribution in groundwater of Taiwan - Y. L. Han; M. C. Tom Kuo; K. C. Fan; C. J. Chiang; Y. P. Lee (Hydrogeology Journal, 2006)

Mycobacterium lentiflavum, a recently identified slow-growing mycobacterial species: clinical significance in immunosuppressed cancer patients and summary of reported cases of infection - A. Safdar; X. Y. Han (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Seasonal Variation of Chemical Composition in Fine Particles at Gosan, Korea - J. S. Han; K. J. Moon; B. J. Kong; S. J. Lee; J. E. Kim; Y. J. Kim (Environmental Monitoring and Assessment, 2005)

Arsenic, Cadmium, Chromium, Cobalt, and Copper in Different Types of Chinese Tea - W.-Y. Han; Y.-Z. Shi; L.-F. Ma; J.-Y. Ruan (Bulletin of Environmental Contamination and Toxicology, 2005)

Inhibiting the Sexual Behavior of Female Cotton Bollworm Helicoverpa armigera - W. X. Dong; B. Y. Han; J. W. Du (Journal of Insect Behavior, 2005)

Trends of summer dry spells in China during the late twentieth century - D.-Y. Gong; J.-A. Wang; H. Han (Meteorology and Atmospheric Physics, 2005)

Phosphorus characteristics correlate with soil fertility of albic luvisols - X. Z. Han; C. Tang; C. Y. Song; S. Y. Wang; Y. F. Qiao (Plant and Soil, 2005)

Decoding the Decoding Region: Analysis of Eukaryotic Release Factor (eRF1) Stop Codon-Binding Residues - Han Liang; Jonathan Y. Wong; Qing Bao; Andre R.O. Cavalcanti; Laura F. Landweber (Journal of Molecular Evolution, 2005)

Effects of Acid Precipitation and Aluminum on Carbohydrate Metabolism in Mycorrhizae of Pinus massioniana - J. K. Tan; F. X. Kong; H. S. Cao; Y. Yu; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2005)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Nonylphenol Induced Apoptosis in Rat Testis Through the Fas/FasL Pathway - X. Han; Z. Tu; X. Wang; S. Shen; Y. Hou (Bulletin of Environmental Contamination and Toxicology, 2004)

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea - G. Yi; S.-K. Lee; Y.-K. Hong; Y.-C. Cho; M.-H. Nam; S.-C. Kim; S.-S. Han; G.-L. Wang; T.-R. Hahn; P.C. Ronald; J.-S. Jeon (Theoretical and Applied Genetics, 2004)

Activation of a rice endogenous retrotransposon Tos17 in tissue culture is accompanied by cytosine demethylation and causes heritable alteration in methylation pattern of flanking genomic regions - Z. L. Liu; F. P. Han; M. Tan; X. H. Shan; Y. Z. Dong; X. Z. Wang; G. Fedak; S. Hao; Bao Liu (Theoretical and Applied Genetics, 2004)

Characteristics of Ion Components and Trace Elements of Fine Particles at Gosan, Korea in Spring time from 2001 to 2002 - J. S. Han; K. J. Moon; J. Y. Ahn; Y. D. Hong; Y. J. Kim; S. Y. Ryu; S. S. Cliff; T. A. Cahill (Environmental Monitoring and Assessment, 2004)

Infections by the Yeast Kodomaea ( Pichia ) ohmeri : Two Cases and Literature Review - X. Y. Han; J. J. Tarrand; E. Escudero (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Nitrous Oxide Emission and Urease Activity in Wheat - H. Bai; Y. Zhang; J. Han; C. Li (Bulletin of Environmental Contamination and Toxicology, 2003)

Some technical aspects of magnetic stimulation coil design with the ferromagnetic effect - B. H. Han; S. Y. Lee; J. H. Kim; J. H. Yi (Medical & Biological Engineering & Computing, 2003)

Distribution and Sources of PAHs in Saemangeum Reclaimed Tidal Lands of Central Korea - J. Y. Cho; K. W. Han; J. H. Kim; J. K. Son; K. S. Yoon (Bulletin of Environmental Contamination and Toxicology, 2003)

Effect of Nonylphenol on Apoptosis of Sertoli Cells in Vitro - X. Wang; X. Han; Y. Hou; G. Yao; Y. Wang (Bulletin of Environmental Contamination and Toxicology, 2003)

Excitability of the ipsilateral motor cortex during phasic voluntary hand movement - Young H. Sohn; Han Y. Jung; Alain Kaelin-Lang; Mark Hallett (Experimental Brain Research, 2003)

Characterization of genotype II Rubella virus strains - D.-P. Zheng; Y. M. Zhou; K. Zhao; Y.-R. Han; T. K. Frey (Archives of Virology, 2003)

The complete nucleotide sequence of Beet black scorch virus (BBSV), a new member of the genus Necrovirus - Y. Cao; Z. Cai; Q. Ding; D. Li; C. Han; J. Yu; Y. Liu (Archives of Virology, 2002)

Perturbations of Population Growth in a Microcosm by Industrial Metal Plating and Ice Cream Mills Wastewater and Landfill Leachate - S.-U. Wui; K. Cho; Y. Inamori; J.-S. Lee; M.-S. Han; J.-B. Lee (Bulletin of Environmental Contamination and Toxicology, 2002)

Cadmium-Induced Apoptosis in H9c2, A7r5, and C6-Glial Cell - M. K. Choi; B. H. Kim; Y. Y. Chung; M. S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Response-Surface Analysis for the Inhibition Toxicity of Benzene Derivatives to Yeast Saccharomyces cerevisiae - X. Wang; Y. Wang; X. Dai; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Mass production of Siberian ginseng plantlets through large-scale tank culture of somatic embryos - Choi Y.-E.; Lee K.-S.; Kim E.-Y.; Kim Y.-S.; Han J.-Y.; Kim H.-S.; Jeong J.-H.; Ko S.-K. (Plant Cell Reports, 2002)

The influence of inverted repeats on the production of small antisense RNAs involved in gene silencing - Y. Han; D. Grierson (Molecular Genetics and Genomics, 2002)

Differential distribution of interneurons in the neural networks that control walking in the mudpuppy (Necturus maculatus) spinal cord - J. Cheng; K. Jovanovic; Y. Aoyagi; D. J. Bennett; Y. Han; R. B. Stein (Experimental Brain Research, 2002)

The exotic American eel in Taiwan: ecological implications - Y.‐S. Han; C.‐H. Yu; H.‐T. Yu; C.‐W. Chang; I‐C. Liao; W.‐N. Tzeng (Journal of Fish Biology, 2002)
Six American eels Anguilla rostrata were identified in the Kaoping River of south‐western Taiwan by sequencing the mitochondrial cytochrome b gene ( mtCyt‐b ). This was the first record of an exotic eel species in the natural waters of Taiwan. The exotic eels may have been imported from North America at the elver stage for aquaculture and escaped from culture ponds.

Comparative Inhibition and Quantitative Structure-Activity Relationships (QSARs) of Substituted Phenols to Germination Rate of Cucumis sativus - X. Wang; X. Yang; Y. Wang; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

An Assessment of the RAIM Performance of a Combined Galileo/GPS Navigation System Using the Marginally Detectable Errors (MDE) Algorithm - W. Y. Ochieng; K. F. Sheridan; K. Sauer; X. Han; P. A. Cross; S. Lannelongue; N. Ammour; K. Petit (GPS Solutions, 2002)

From simulation to implementation: low-cost densification of permanent GPS networks in support of geodetic applications - H.-Y. Chen; C. Rizos; S. Han (Journal of Geodesy, 2001)

Origin of laminated diatom ooze in King George Basin sediments from Bransfield Strait, Antarctica - H. I. Yoon; B. K. Park; M. W. Han; B. K. Khim; Y. Kim; C. Y. Kang (Geosciences Journal, 2001)

Physical and Chemical Properties of a Winter-Time Yellow Sand Event in Northeast Asia - B. G. Kim; J. Y. Ahn; H. R. Noh; C. J. Park; J. S. Han; S. U. Park (Water, Air, & Soil Pollution, 2001)

Sequence diversity and interrelationships among isolates of satsuma dwarf-related viruses - T. Iwanami; Y. Kondo; M. Kobayashi; S. S. Han; A. V. Karasev (Archives of Virology, 2001)

Identification of rice black-streaked dwarf fijivirus in maize with rough dwarf disease in China - S. Fang; J. Yu; J. Feng; C. Han; D. Li; Y. Liu (Archives of Virology, 2001)

Sequence variants and functional analysis of human papillomavirus type 16 E5 gene in clinical specimens - C.-H. Hsieh; Y.-P. Tsao; C.-H. Wang; C.-P. Han; J.-L. Chang; J.-Y. Lee; S.-L. Chen (Archives of Virology, 2000)

Adaptive filtering of continuous GPS results - L. Ge; H.-Y. Chen; S. Han; C. Rizos (Journal of Geodesy, 2000)

Structure-phytotoxicity relationship: Comparative inhibition of selected nitrogen containing aromatics to root elongation of Cucumis sativus - X. Wang; Y. Dong; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 2000)

Quantitative Structure-Activity Relationships for the Toxicity to the Tadpole Rana japonica of Selected Phenols - X. Wang; Y. Dong; S. Xu; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2000)

An integrated genetic map of Populus deltoides based on amplified fragment length polymorphisms - R. L. Wu; Y. F. Han; J. J. Hu; J. J. Fang; L. Li; M. L. Li; Z. -B. Zeng (Theoretical and Applied Genetics, 2000)

Quantitative Structure-Activity Relationships for the Toxicity to the Tadpole Rana japonica of Selected Phenols - X. Wang; Y. Dong; S. Xu; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2000)

Nitrogen in percolation water in paddy fields with a rice/wheat rotation - J.G. Zhu; Y. Han; G. Liu; Y.L. Zhang; X.H. Shao (Nutrient Cycling in Agroecosystems, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

The nucleotide sequence of a Chinese isolate of wheat yellow mosaic virus and its comparison with a Japanese isolate - D. Li; L. Yan; N. Su; C. Han; Z. Hou; J. Yu; Y. Liu (Archives of Virology, 1999)

Genetic transformation of Cymbidium orchid by particle bombardment - J. Yang; H.-J. Lee; D. H. Shin; S. K. Oh; J. H. Seon; K. Y. Paek; K.-H. Han (Plant Cell Reports, 1999)

Evidence for Overlapping Substrate Specificity Between Large Neutral Amino Acid (LNAA) and Dipeptide (hPEPTl) Transporters for PD 158473, an NMDA Antagonist - Narayanan Surendran; Kuang-Ming Y. Covitz; Hyo-kyung Han; Wolfgang Sadee; Doo-Man Oh; Gordon L. Amidon; Rufus M. Williamson; Christopher F. Bigge; Barbra H. Stewart (Pharmaceutical Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Expression of bvgAS of Bordetella pertussis represses flagellar biosynthesis of Escherichia coli - Y. W. Han; M. A. Uhl; Seog Joon Han; W. Shi (Archives of Microbiology, 1999)

Estimation of Target Hazard Quotients and Potential Health Risks for Metals by Consumption of Seafood in Taiwan - B.-C. Han; W. L. Jeng; R. Y. Chen; G. T. Fang; T. C. Hung; R. J. Tseng (Archives of Environmental Contamination and Toxicology, 1998)

5′-Amino Acid Esters of Antiviral Nucleosides, Acyclovir, and AZT Are Absorbed by the Intestinal PEPT1 Peptide Transporter - Hyo-kyung Han; Remco L. A. de Vrueh; Julie K. Rhie; Kuang-Ming Y. Covitz; Philip L. Smith; Chao-Pin Lee; Doo-Man Oh; Wolfgang Sadee; Gordon L. Amidon1 (Pharmaceutical Research, 1998)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)

cGMP facilitates calcium current via cGMP-dependent protein kinase in isolated rabbit ventricular myocytes - J. Han; Euiyong Kim; S. H. Lee; S. Yoo; Won-Kyung Ho; Y. E. Earm (Pflügers Archiv - European Journal of Physiology, 1998)

Rock-Shells ( Thais clavigera ) as an Indicator of As, Cu, and Zn Contamination on the Putai Coast of the Black-Foot Disease Area in Taiwan - B. C. Han; W. L. Jeng; M. S. Jeng; L. T. Kao; P. J. Meng; Y. L. Huang (Archives of Environmental Contamination and Toxicology, 1997)

Chirp (2–7 kHz) echo characters in the Ulleung Basin - S. K. Chough; S. H. Lee; J. W. Kim; S. C. Park; D. G. Yoo; H. S. Han; S. H. Yoon; S. B. Oh; Y. B. Kim; G. G. Back (Geosciences Journal, 1997)

Identification of a rat brain gene associated with aging by PCR differential display method - Han C. Wu; Eminy H. Y. Lee (Journal of Molecular Neuroscience, 1997)

Effect of EHS matrix on expression of transgenes in HC11 cells - T. H. Lee; M. G. Baik; W. B. Im; C. S. Lee; Y. M. Han; S. J. Kim; K. K. Lee; Y. J. Choi (In Vitro Cellular & Developmental Biology - Animal, 1997)

Monitoring lead pollution near a storage battery recycling plant in Taiwan, Republic of China - C. -Y. Yeh; H. -Y. Chiou; R. -Y. Chen; K. -H. Yeh; W. -L. Jeng; B. -C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Monitoring Lead Pollution Near a Storage Battery Recycling Plant in Taiwan, Republic of China - C.-Y. Yeh; H.-Y. Chiou; R.-Y. Chen; K.-H. Yeh; W.-L. Jeng, B.-C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Nucleotide sequence of the human? 1-globin gene - J. M. Gonzalez-Redondo; I. S. Han; Y. -C. Gu; T. H. J. Huisman (Biochemical Genetics, 1988)

Mirex in human milk in upstate New York - B. Bush; J. Snow; S. Connor; L. Rueckert; Y. Han; P. Dymerski; D. Hilker (Archives of Environmental Contamination and Toxicology, 1983)